Method for producing sulfide solid electrolyte

By mixing the composite containing lithium and halogen at a specific temperature and pressure, the problems of long reaction time and low ionic conductivity in the production of sulfide solid electrolytes are solved, and the manufacturing of sulfide solid electrolytes with high purity and high conductivity is achieved.

JP7627612B2Active Publication Date: 2025-02-06IDEMITSU KOSAN CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021078663
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-07
Filing Date
2021-05-06
Publication Date
2025-02-06
Estimated Expiration
2041-05-06

AI Technical Summary

Technical Problem

In the production of sulfide solid electrolytes, the problems of long reaction time, low ionic conductivity and difficult component separation are present. Especially in the liquid phase method, the separation of electrolyte components and solvent residues are easily caused during dissolution and precipitation, which affects the purity and conductivity of the electrolyte.

Method used

By mixing complexes containing lithium atoms, sulfur atoms and phosphorus atoms (Complex 1) with complexes containing lithium atoms and halogen atoms (Complex 2) and reacting at specific temperatures and pressures to form a high-purity sulfide solid electrolyte. The rapid reactions and limited side reactions between the complexes are used to improve ionic conductivity.

Benefits of technology

The production of sulfide solid electrolytes with high purity and high ionic conductivity is achieved, which simplifies the manufacturing process, reduces the occurrence of side reactions, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627612000003
    Figure 0007627612000003
  • Figure 0007627612000004
    Figure 0007627612000004
  • Figure 0007627612000005
    Figure 0007627612000005
Patent Text Reader

Abstract

To provide a method for conveniently producing a sulfide solid electrolyte having a high purity as side reaction hardly occurs, and having a high ionic conductivity.SOLUTION: The present invention discloses a method for producing a sulfide solid electrolyte containing a lithium atom, a sulfur atom, a phosphorus atom and a halogen atom, the method comprising separately preparing a complex (1) containing a sulfide that contains a lithium atom, a sulfur atom and a phosphorus atom, as a constituent element, and a complex (2) containing a halide that contains a lithium atom and a halogen atom, as a constituent element, and mixing the complex (1) and the complex (2).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a sulfide solid electrolyte. [Background technology]

[0002] In recent years, with the rapid spread of information-related devices and communication devices such as personal computers, video cameras, and mobile phones, the development of batteries to be used as power sources for these devices has become important. Conventionally, electrolytes containing flammable organic solvents have been used in batteries used for such purposes, but by making the battery fully solid-state, flammable organic solvents are not used in the battery, safety devices can be simplified, and manufacturing costs and productivity are excellent, so that batteries in which the electrolyte is replaced with a sulfide solid electrolyte layer are being developed.

[0003] The methods for producing the sulfide solid electrolyte used in the sulfide solid electrolyte layer are roughly divided into a solid-phase method and a liquid-phase method. The liquid-phase method includes a homogeneous method in which the sulfide solid electrolyte material is completely dissolved in a solvent, and a heterogeneous method in which the sulfide solid electrolyte material is not completely dissolved and a solid-liquid coexistence suspension is formed. For example, as a solid-phase method, a method is known in which raw materials such as lithium sulfide and diphosphorus pentasulfide are subjected to mechanical milling treatment using a device such as a ball mill or a bead mill, and then heated as necessary to produce an amorphous or crystalline sulfide solid electrolyte (see, for example, Patent Document 1). According to this method, a sulfide solid electrolyte is obtained by applying mechanical stress to raw materials such as lithium sulfide to promote a reaction between solids.

[0004] On the other hand, as a homogeneous liquid phase method, a method in which a sulfide solid electrolyte is dissolved in a solvent and reprecipitated is known (see, for example, Patent Document 2), and as a heterogeneous method, a method in which a sulfide solid electrolyte raw material such as lithium sulfide is reacted in a solvent containing a polar aprotic solvent is known (see Patent Documents 3 and 4, and Non-Patent Document 1). For example, Patent Document 4 discloses a method for producing a sulfide solid electrolyte with a Li4PS4I structure, which includes a step of using dimethoxyethane (DME) and combining it with a Li3PS4 structure to obtain Li3PS4·DME. The ionic conductivity of the obtained sulfide solid electrolyte is 5.5×10 -5 S / cm (Calcium doped: 3.9 × 10 -4 In recent years, the liquid phase method has been attracting attention as a method that can be easily and mass-produced in addition to its versatility and applicability in order to commercialize all-solid-state batteries. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2017 / 159667 Brochure [Patent Document 2] JP 2014-191899 A [Patent Document 3] International Publication No. 2014 / 192309 Brochure [Patent Document 4] International Publication No. 2018 / 054709 Brochure [Non-patent literature]

[0006] [Non-Patent Document 1] “CHEMISTRY OF MATERIALS”, 2017, No. 29, pp. 1830-1835 Summary of the Invention [Problem to be solved by the invention]

[0007] However, conventional solid-phase methods involving mechanical milling and the like are centered on solid-phase reactions, and although they can easily produce sulfide solid electrolytes with high purity and thus realize high ionic conductivity, they have the problem of long reaction times. In the liquid phase method, the sulfide solid electrolyte is dissolved, which causes some of the sulfide solid electrolyte components to decompose or be lost during precipitation, making it difficult to achieve high ionic conductivity compared to the solid phase synthesis method. For example, in the homogeneous method, the raw materials and sulfide solid electrolyte are completely dissolved once, so that the components can be uniformly dispersed in the liquid. However, in the subsequent precipitation process, precipitation proceeds according to the solubility specific to each component, so it is extremely difficult to maintain the dispersion state of the components while precipitation. As a result, each component separates and precipitates. In addition, in the homogeneous method, the affinity between the solvent and lithium becomes too strong, so the solvent is difficult to remove even when dried after precipitation. For these reasons, the homogeneous method has the problem that the ionic conductivity of the sulfide solid electrolyte is significantly reduced. In addition, even in a solid-liquid coexistence heterogeneous method, a part of the sulfide solid electrolyte dissolves, and separation occurs due to elution of specific components, making it difficult to obtain a desired sulfide solid electrolyte.

[0008] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a method for simply producing a sulfide solid electrolyte that is highly pure and has high ionic conductivity because side reactions and the like are unlikely to occur. [Means for solving the problem]

[0009] As a result of intensive research aimed at solving the above problems, the present inventors have discovered the following and have completed the present invention. 1. By preparing the complex (1) described below and the complex (2) described below, respectively, it is possible to obtain a sulfide solid electrolyte having high ionic conductivity while preventing side reactions and the like from occurring and suppressing the elution of halogen atoms from within the crystals.

[0010] 2. By mixing complex (1) described below with complex (2) described below, the reaction between complex (1) and complex (2) proceeds rapidly, making it possible to easily obtain a sulfide solid electrolyte having high ionic conductivity.

[0011] That is, the present invention provides the following [1] to

[17] . [1] A method for producing a sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, the method comprising: preparing a complex (1) containing a sulfide containing lithium atoms, sulfur atoms, and phosphorus atoms as components; and preparing a complex (2) containing a halide containing lithium atoms and halogen atoms as components; and mixing complex (1) and complex (2). [2] The method for producing a sulfide solid electrolyte according to [1], further comprising heating the complex (1) after mixing the complex (2). [3] The method for producing a sulfide solid electrolyte according to [2], wherein the heating is carried out at 90 to 250°C.

[0012] [4] The method for producing a sulfide solid electrolyte according to [2] or [3], wherein the heating is carried out at 0.1 to 100.0 Pa. [5] The method for producing a sulfide solid electrolyte according to any one of [1] to [4], wherein the mixing is carried out in a solvent. [6] The method for producing a sulfide solid electrolyte according to any one of [1] to [5], wherein the mixing is carried out using a pulverizer.

[0013] [7] The method for producing a sulfide solid electrolyte according to any one of [1] to [6], wherein the sulfide contains amorphous Li3PS4 or crystalline Li3PS4. [8] The method for producing a sulfide solid electrolyte according to any one of [1] to [7], wherein the complex (1) further contains a complexing agent (1) as a component, and the complex (2) further contains a complexing agent (2) as a component. [9] The method for producing a sulfide solid electrolyte according to [8], wherein the complexing agent (1) and the complexing agent (2) each independently contain a compound having a heteroatom.

[0014]

[10] The method for producing a sulfide solid electrolyte according to [8] or [9], wherein the complexing agent (1) and the complexing agent (2) each independently contain a compound having at least one amino group or an ether bond.

[11] The method for producing a sulfide solid electrolyte according to any one of [8] to

[10] , wherein the complexing agent (1) and the complexing agent (2) each independently contain a compound having at least two tertiary amino groups in the molecule.

[12] The method for producing a sulfide solid electrolyte according to any one of [8] to

[11] , wherein the complex (1) and the complex (2) are mixed to obtain a precursor containing the complexing agent (1), the complexing agent (2), a lithium atom, a sulfur atom, a phosphorus atom and a halogen atom as constituent components.

[0015]

[13] The method for producing a sulfide solid electrolyte according to

[12] , wherein a total content of the complex (1) and the complex (2) in the precursor is 30 to 80 mass% based on a total amount of the precursor.

[14] The method for producing a sulfide solid electrolyte according to any one of [5] to

[13] , wherein the solvent is at least one solvent selected from an aliphatic hydrocarbon solvent, an alicyclic hydrocarbon solvent, an aromatic hydrocarbon solvent, and an ether solvent.

[15] The method for producing a sulfide solid electrolyte according to any one of [5] to

[14] , wherein 5 to 50 mL of the solvent is used per 1 g of the total mass of the complex (1) and the complex (2).

[0016]

[16] The method for producing a sulfide solid electrolyte according to any one of [1] to

[15] , wherein the sulfide solid electrolyte contains a thiolicon region II type crystal structure.

[17] The method for producing a sulfide solid electrolyte according to any one of [1] to

[16] , wherein the sulfide solid electrolyte does not have diffraction peaks at 2θ=17.5° and 26.1° corresponding to crystalline Li3PS4 in X-ray diffraction measurement using CuKα radiation. Effect of the Invention

[0017] According to the present invention, it is possible to provide a method for simply producing a sulfide solid electrolyte having high purity and high ionic conductivity because side reactions and the like are unlikely to occur. [Brief description of the drawings]

[0018] [Figure 1] FIG. 2 is a flow chart illustrating an example of a preferred embodiment of the manufacturing method of the present embodiment. [Diagram 2] This is an X-ray diffraction (XRD) spectrum (XRD pattern) of the Li3PS4 TMEDA (N,N,N,N-tetramethylethane-1,2-diamine) complex (Li3PS4-TMEDA complex) obtained in the preparation example (2-3). [Diagram 3] 1 is an X-ray diffraction spectrum (XRD pattern) of the LiBr TMEDA complex (LiBr-TMEDA complex) obtained in Preparation Example (3-1). [Figure 4] 1 is an X-ray diffraction spectrum (XRD pattern) of the LiI TMEDA complex (LiI-TMEDA complex) obtained in Preparation Example (3-2). [Diagram 5] This shows the results of TG (differential thermal)-DTA (thermogravimetry) measurements of the Li3PS4-TMEDA complex obtained in the preparation example (2-3). [Figure 6] TG (differential thermal)-DTA (thermogravimetry) measurement results of the LiBr-TMEDA complex obtained in Preparation Example (3-1). [Figure 7] TG (differential thermal)-DTA (thermogravimetry) measurement results of the LiI-TMEDA complex obtained in Preparation Example (3-2). [Figure 8] 1 shows X-ray diffraction spectra of precursors (1) to (3) obtained in Examples 1 to 3. [Figure 9] 1 shows X-ray diffraction spectra (XRD patterns) of the sulfide solid electrolytes obtained in Examples 1 to 3 and Comparative Example 1. [Figure 10] 1 shows X-ray diffraction spectra (XRD patterns) of the sulfide solid electrolytes obtained in Examples 1 and 4. [Figure 11] 1 shows X-ray diffraction spectra (XRD patterns) of the sulfide solid electrolytes obtained in Examples 1 and 5. [Figure 12] FIG. 2 is a schematic diagram of a test device used in an exposure test. [Figure 13] 1 is a graph showing the change over time in the amount of hydrogen sulfide generated in an exposure test. [Figure 14] 1 is a graph showing the change over time in the integrated amount of hydrogen sulfide generated in an exposure test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, an embodiment of the present invention (hereinafter, sometimes referred to as "the present embodiment") will be described. In this specification, the upper and lower limit values ​​of a numerical range expressed by "greater than or equal to", "less than or equal to", and "to" are values ​​that can be arbitrarily combined, and the numerical values ​​in the examples can also be used as the upper and lower limit values.

[0020] [Method for producing sulfide solid electrolyte] The method for producing the sulfide solid electrolyte of the present embodiment is a production method including preparing a complex (1) containing, as components, a sulfide containing lithium atoms, sulfur atoms, and phosphorus atoms, and optionally a complexing agent (1), and a complex (2) containing, as components, a halide containing lithium atoms and halogen atoms, and optionally a complexing agent (2), and mixing the complex (1) with the complex (2).

[0021] In this specification, "comprise" and "comprise as a component" mean not only the literal meaning of "comprise" but also include cases where "comprise" is bonded to other atoms, other molecules, etc., such as cases where at least one atom constituting the compound is included in the compound by bonding to at least one atom constituting another compound while retaining the structure of the compound when mixed.

[0022] In this specification, the term "sulfide solid electrolyte" refers to an electrolyte that maintains a solid state under a nitrogen atmosphere at 25° C. The sulfide solid electrolyte in this embodiment is a sulfide solid electrolyte that contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms and has ionic conductivity due to the lithium atoms.

[0023] The term "sulfide solid electrolyte" includes both a crystalline sulfide solid electrolyte having a crystal structure obtained by the manufacturing method of this embodiment and an amorphous sulfide solid electrolyte. In this specification, the crystalline sulfide solid electrolyte is a sulfide solid electrolyte in which a peak derived from the sulfide solid electrolyte is observed in the X-ray diffraction pattern in an X-ray diffraction measurement, and is a material in which the presence or absence of a peak derived from the raw material of the sulfide solid electrolyte is not an issue. That is, the crystalline sulfide solid electrolyte includes a crystal structure derived from the sulfide solid electrolyte, and a part of the crystal structure may be derived from the sulfide solid electrolyte, or the entire crystal structure may be derived from the sulfide solid electrolyte. And, as long as the crystalline sulfide solid electrolyte has the X-ray diffraction pattern as described above, a part of the crystalline sulfide solid electrolyte may include an amorphous sulfide solid electrolyte. Therefore, the crystalline sulfide solid electrolyte includes so-called glass ceramics obtained by heating the amorphous sulfide solid electrolyte to a crystallization temperature or higher. In this specification, the term "amorphous sulfide solid electrolyte" refers to an amorphous sulfide solid electrolyte in which the X-ray diffraction pattern is a halo pattern in which no peaks other than those derived from the material are observed in X-ray diffraction measurement, and it does not matter whether or not there are peaks derived from the raw materials of the sulfide solid electrolyte.

[0024] The method for producing the sulfide solid electrolyte of this embodiment includes mixing a complex (1) and a complex (2) as described below as shown in Fig. 1, and may include other steps such as drying as described below as necessary. It is preferable to mix the complex (1) and the complex (2) to obtain a precursor as described below. The precursor will be described in detail later, but is preferably obtained by mixing complex (1) and complex (2) complexed with a complexing agent (complexing agent (1) or complexing agent (2) described later), and the sulfide solid electrolyte is formed by removing the complexing agent by drying or the like. Therefore, in this specification, the one obtained by mixing complexes (1) and (2) is referred to as a "precursor". This "precursor" preferably contains complexing agent (1) and complexing agent (2) as components, which will be described later.

[0025] Sulfide solid electrolytes may generate hydrogen sulfide due to hydrolysis reactions that occur when they come into contact with moisture such as humidity in the air. Therefore, the manufacturing process for sulfide solid electrolytes and batteries is ideally carried out in an environment with low moisture and a low dew point, but it is economically and physically difficult to carry out all the processes at a low dew point, and in reality it is required to be able to handle sulfide solid electrolytes at a high dew point (e.g., a dew point of -60 to -20°C) at the dry room level. According to the production method of the present invention, production at a high dew point becomes possible, and this is highly effective in scaling up the production process.

[0026] <Mixed> The mixing in this embodiment is not particularly limited as long as it involves mixing complex (1) and complex (2), and may be mixing by either a liquid phase method or a solid phase method. Furthermore, the liquid phase method may be a homogeneous method in which the sulfide solid electrolyte material is completely dissolved in a solvent and mixed, or a heterogeneous method in which the sulfide solid electrolyte material is not completely dissolved and is mixed via a suspension in which solid and liquid coexist. From the viewpoints of not causing granulation that would increase the particle size during the mixing step and of enabling production at low temperature with simple equipment, it is preferable to carry out the process in a solvent, as in the homogeneous method and heterogeneous method, and from the viewpoints of achieving high ionic conductivity and reducing the environmental load associated with the use of solvents, the solid-phase method is preferable. The complex (1) and the complex (2) may be in the form of a solid or a liquid, but are usually in the form of a solid or a slurry as described below.

[0027] The method for mixing complex (1) and complex (2) is not particularly limited, and the prepared complex (1) and complex (2) may be mixed by putting them into a device capable of mixing them. In order to shorten the mixing time and obtain homogeneous complex (1) and complex (2), it is preferable to mix them in a solvent as described below.

[0028] The method for producing a sulfide solid electrolyte of this embodiment includes mixing complex (1) and complex (2). The device for mixing is not particularly limited as long as it can at least mix, but it is preferable to use a pulverizer. For example, a device generally called a pulverizer, such as a media type pulverizer such as a ball mill or a bead mill, which is used for the purpose of pulverizing solid raw materials, may be used, or the mixture may be mixed in a solvent using, for example, a mechanical stirring type mixer equipped with stirring blades in a tank.

[0029] The mill used for mixing is not particularly limited as long as it can mix particles, and for example, a media type mill using a grinding medium can be used. Among the media type mills, a wet type mill that can handle wet grinding is preferable, considering that the precursor is mainly in a liquid state accompanied by liquids such as a complexing agent and a solvent, or in a slurry state. Representative examples of wet grinding machines include wet bead mills, wet ball mills, and wet vibration mills, and wet bead mills using beads as grinding media are preferred because they allow the mixing conditions to be freely adjusted and are easy to handle smaller particle sizes. Dry grinding machines such as dry media grinding machines such as dry bead mills, dry ball mills, and dry vibration mills, and dry non-media grinding machines such as jet mills can also be used. Depending on the amount of the mixture, it may be possible to mix the mixture using a mortar or the like.

[0030] In addition, when the precursor mixed in the pulverizer is in a slurry state, it is preferable to use a flow-type pulverizer that can perform a circulation operation to circulate the precursor as necessary. More specifically, it is preferable to use a pulverizer that circulates the precursor between a pulverizer (pulverizing mixer) that mixes the slurry and a temperature holding tank (reaction vessel), as described in JP-A-2010-140893.

[0031] The size of the beads used in the above-mentioned grinding machine may be appropriately selected depending on the desired particle size, processing amount, etc. For example, the diameter of the beads may be about 0.05 mmφ or more and 5.0 mmφ or less, preferably 0.1 mmφ or more and 3.0 mmφ or less, and more preferably 0.3 mmφ or more and 2.5 mmφ or less.

[0032] The material of the beads used in the above-mentioned pulverizer can be appropriately selected from titania, alumina, and zirconia.

[0033] Mechanical agitation mixers include high-speed agitation mixers and double-arm mixers, and are used to mix sulfides and halides. In order to improve the uniformity of the raw materials in the mixture of the raw material contents (hereinafter also referred to as raw material contents) and the complexing agent and to obtain a higher ionic conductivity, a high-speed stirring mixer is preferably used. Examples of the high-speed stirring mixer include a vertical axis rotary mixer and a horizontal axis rotary mixer, and either type of mixer may be used.

[0034] Examples of the shape of the impeller used in the mechanical stirring mixer include blade type, arm type, ribbon type, multi-stage blade type, double arm type, shovel type, double-shaft blade type, flat blade type, C-shaped blade type, etc., and from the viewpoint of increasing the uniformity of the raw material in the raw material content and obtaining higher ionic conductivity, the shovel type, flat blade type, C-shaped blade type, etc. are preferred. Depending on the amount of the mixture, a stirring bar may be used to stir the mixture using a mechanical stirrer.

[0035] The temperature condition when mixing complex (1) and complex (2) is not particularly limited, and is, for example, −30 to 100° C., preferably −10 to 50° C., and more preferably about room temperature (23° C.) (for example, about room temperature ±5° C.). The mixing time is about 0.1 to 150 hours in the case of a solid phase method, and from the viewpoint of more uniform mixing and obtaining higher ionic conductivity, it is preferably 1 to 120 hours, more preferably 2 to 100 hours. The mixing time is preferably about 0.1 to 100 hours in the case of a liquid phase method, and when the complexing agent, which is a component of the complex, is an amine compound described below, the mixing time is preferably 1 to 50 hours, more preferably 2 to 10 hours, from the viewpoint of more uniform mixing and obtaining higher ionic conductivity. When the complexing agent, which is a component of the complex, is an amine compound described below, for example an ether compound, the mixing time is preferably 20 to 90 hours, more preferably 30 to 80 hours, from the viewpoint of more uniform mixing and obtaining higher ionic conductivity.

[0036] By mixing complex (1) containing a sulfide containing lithium atoms, sulfur atoms, and phosphorus atoms as a component, and complex (2) containing a halide containing lithium atoms and halogen atoms as a component, the action of the lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms contained in complex (1) and complex (2) with the complexing agent is promoted. This allows a precursor to be obtained in which the atoms contained in the sulfide and the halide are directly bonded to each other via and / or without the complexing agent. That is, in the method for producing a sulfide solid electrolyte of this embodiment, the precursor obtained by mixing complex (1) and complex (2) is composed of a complexing agent, lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, and by mixing the above complex (1) and complex (2), a material containing the precursor is obtained.

[0037] In this way, by separately preparing complex (1) and complex (2) and mixing them, halogen atoms and sulfur atoms can be incorporated into the precursor as described above. Furthermore, by separately preparing complex (1) and complex (2), it is possible to suppress by-products, and it is also possible to remove by-products during the preparation of complex (1) and by-products during the preparation of complex (2), thereby improving the purity of the precursor. In addition, since the reaction is between complexes such as complex (1) and complex (2), it is possible to shorten the reaction time. In this embodiment, when mixing is performed in a solvent, the precursor obtained is usually obtained as a suspension (slurry) containing the precursor which is a solid, but it may be subsequently made into a powder form by a drying step described later.

[0038] <Complex (1)> The complex (1) of this embodiment contains a sulfide, which will be described later, as a component, and may further contain a complexing agent (1), which will be described later, as a component. These may be used alone or in combination of two or more. Complex (1) preferably contains amorphous Li3PS4 or crystalline Li3PS4. The content of the complexing agent (1) in the complex (1) is preferably 10 mass % or more, more preferably 20 mass % or more, and even more preferably 30 mass % or more, based on the total amount of the complex (1), from the viewpoint of obtaining a solid electrolyte having high ionic conductivity, and is preferably 80 mass % or less, more preferably 70 mass % or less, and even more preferably 60 mass % or less, from the viewpoint of crystal formation.

[0039] The complex (1) is preferably in the form of particles, and the average particle size (D 50 ) is preferably 10 μm or more and 2000 μm or less, more preferably 30 μm or more and 1500 μm or less, and even more preferably 50 μm or more and 1000 μm or less. In this specification, the average particle size (D 50 ) is the particle size at which the particle size distribution is accumulated from the smallest particle size to 50% of the total when a particle size distribution cumulative curve is drawn, and the volume distribution is the average particle size that can be measured, for example, using a laser diffraction / scattering particle size distribution measuring device. Complex (2) described later preferably has an average particle size approximately the same as that of complex (1), that is, preferably within the same range as that of complex (1).

[0040] (sulfide) The sulfide of this embodiment contains lithium atoms, sulfur atoms, and phosphorus atoms, and is preferably Li3PS4 or the like having a PS4 structure, etc. In the production method of this embodiment, a structure containing lithium, such as Li3PS4, which exists as a main structure in the solid electrolyte, is used as a raw material, and therefore the composition ratio of the structure can be increased and the ion conductivity is improved compared to the case of producing a sulfide solid electrolyte without going through the sulfide of this embodiment as in Patent Document 3 and the like.

[0041] The sulfide of this embodiment preferably contains amorphous Li3PS4 or crystalline Li3PS4. By using the complex containing the sulfide of this embodiment as a constituent element and mixing it with the complex (2) described below, it becomes easier to obtain a sulfide solid electrolyte in which halogen atoms are dispersed and fixed, resulting in a sulfide solid electrolyte with high ionic conductivity. As the raw material for the sulfide, for example, a compound containing at least one selected from a lithium atom, a sulfur atom, and a phosphorus atom can be used alone or in combination.

[0042] In this way, from the viewpoint of easily obtaining a sulfide solid electrolyte having high ionic conductivity by using a complex having a sulfide as a constituent element, examples of the raw materials include phosphorus sulfides such as lithium sulfide (LiS), diphosphorus trisulfide (P2S3), and diphosphorus pentasulfide (P2S5), and a preferred combination of the raw materials is, for example, a combination of lithium sulfide and diphosphorus pentasulfide.

[0043] When Li3PS4 prepared from lithium sulfide and diphosphorus pentasulfide is used as the sulfide, the ratio of lithium sulfide to the total of lithium sulfide and diphosphorus pentasulfide is preferably 70 to 80 mol%, more preferably 72 to 78 mol%, and even more preferably 74 to 76 mol%, from the viewpoint of obtaining higher chemical stability and higher ionic conductivity.

[0044] Furthermore, if necessary, lithium compounds such as lithium oxide, lithium hydroxide, and lithium carbonate; alkali metal sulfides such as sodium sulfide, potassium sulfide, rubidium sulfide, and cesium sulfide; metal sulfides such as silicon sulfide, germanium sulfide, boron sulfide, gallium sulfide, tin sulfide (SnS, SnS2), aluminum sulfide, and zinc sulfide; and phosphate compounds such as sodium phosphate and lithium phosphate may be used.

[0045] (Complexing Agent (1)) In the method for producing a sulfide solid electrolyte of the present embodiment, the use of complexing agent (1) and complexing agent (2) as the complexing agents is preferable because it makes it easier to obtain complex (1) and complex (2), and therefore a solid electrolyte having high ionic conductivity can be obtained. The complexing agent (1) and a complexing agent (2) described below may be the same or different, but it is preferable that they are the same.

[0046] In this specification, the complexing agent (complexing agent (1) and complexing agent (2) described below) is a compound that forms a complex with the sulfide, which is a component of complex (1), and the halide, which is a component of complex (2). The complexing agent is preferably a substance that can form a complex with a lithium atom, a phosphorus atom, a sulfur atom, a halogen atom, or the like, and more preferably has a property of reacting with the sulfide, which is a component of complex (1) containing a lithium atom, or the halide, which is a component of complex (2), to promote the formation of the precursor.

[0047] The complexing agent can be used without any particular limitation as long as it has the above-mentioned properties, and is preferably a compound containing an atom having a high affinity with lithium atoms, such as a nitrogen atom, an oxygen atom, a chlorine atom, or other heteroatom, and more preferably a compound having a group containing such a heteroatom, because such a heteroatom or group containing such a heteroatom can be coordinated (bonded) with lithium.

[0048] The complexing agent has a heteroatom in its molecule that has a high affinity with lithium atoms, and is considered to have a property that is likely to form an aggregate by bonding with a lithium-containing structure such as Li3PS4, which typically contains a PS4 structure, and a raw material containing lithium such as lithium halide, which exists as a main structure in the sulfide solid electrolyte obtained by the manufacturing method of this embodiment. Therefore, by mixing the above-mentioned raw material content with the complexing agent, a lithium-containing structure such as a PS4 structure or an aggregate via a complexing agent, a raw material containing lithium such as lithium halide or an aggregate via a complexing agent are evenly present, and a precursor in which halogen atoms are more dispersed and fixed is obtained, and as a result, it is considered that a sulfide solid electrolyte having high ion conductivity and suppressed generation of hydrogen sulfide is obtained.

[0049] Therefore, it is preferred that the complexing agent (1) and the complexing agent (2) each independently be a compound having a heteroatom. Furthermore, it is preferable that the molecule has at least two heteroatoms capable of coordination (bonding), and more preferable that the molecule has a group containing at least two heteroatoms. By having a group containing at least two heteroatoms in the molecule, it is possible to bond the sulfide, which is a lithium-containing structure such as Li3PS4 containing a PS4 structure, which is a component of complex (1), and the lithium-containing raw material such as lithium halide, which is a component of complex (2), through at least two heteroatoms in the molecule by mixing complex (1) and complex (2). This allows the halogen atoms to be more dispersed and fixed in the precursor. As a result, a sulfide solid electrolyte having high ionic conductivity and suppressed generation of hydrogen sulfide is obtained. Among the heteroatoms, oxygen atoms or nitrogen atoms are preferable, and nitrogen atoms are more preferable. When an oxygen atom is contained, it is preferable to have an ether bond in the molecule, and an amino group is preferable as the group containing a nitrogen atom, that is, an amine compound is preferable as the complexing agent. For this reason, it is preferred that the complexing agent (1) and the complexing agent (2) each independently contain a compound having at least one amino group or ether bond.

[0050] The amine compound is not particularly limited as long as it has an amino group in the molecule, since it can promote the formation of the precursor, but a compound having at least two amino groups in the molecule is preferred. By having such a structure, a sulfide containing lithium such as Li3PS4 containing a PS4 structure and lithium such as lithium halide can be bonded via at least two nitrogen atoms in the molecule, so that the halogen atoms are more dispersed and fixed in the precursor, and as a result, a sulfide solid electrolyte with high ionic conductivity is obtained. For this reason, it is preferred that the complexing agent (1) and the complexing agent (2) each independently contain a compound having at least two tertiary amino groups in the molecule.

[0051] Examples of such amine compounds include aliphatic amines, alicyclic amines, heterocyclic amines, and aromatic amines, and these can be used alone or in combination of two or more kinds.

[0052] More specifically, representative and preferred examples of the aliphatic amine include aliphatic primary diamines such as ethylenediamine, diaminopropane, and diaminobutane; aliphatic secondary diamines such as N,N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N'-dimethyldiaminopropane, and N,N'-diethyldiaminopropane; and aliphatic tertiary diamines such as N,N,N',N'-tetramethyldiaminomethane, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, N,N,N',N'-tetramethyldiaminopropane, N,N,N',N'-tetraethyldiaminopropane, N,N,N',N'-tetramethyldiaminobutane, N,N,N',N'-tetramethyldiaminopentane, and N,N,N',N'-tetramethyldiaminohexane. In the examples given in this specification, for example, in the case of diaminobutane, unless otherwise specified, all isomers are included, such as isomers relating to the position of the amino group, such as 1,2-diaminobutane, 1,3-diaminobutane, and 1,4-diaminobutane, as well as linear and branched isomers for butane. The number of carbon atoms in the aliphatic amine is preferably 2 or more, more preferably 4 or more, and even more preferably 6 or more, with the upper limit being preferably 10 or less, more preferably 8 or less, and even more preferably 7 or less. The number of carbon atoms in the hydrocarbon group of the aliphatic hydrocarbon group in the aliphatic amine is preferably 2 or more, and the upper limit being preferably 6 or less, more preferably 4 or less, and even more preferably 3 or less.

[0053] Representative and preferred examples of the alicyclic amine include alicyclic primary diamines such as cyclopropanediamine and cyclohexanediamine; alicyclic secondary diamines such as bisaminomethylcyclohexane; and alicyclic tertiary diamines such as N,N,N',N'-tetramethyl-cyclohexanediamine and bis(ethylmethylamino)cyclohexane. Representative and preferred examples of the heterocyclic amine include heterocyclic primary diamines such as isophoronediamine; heterocyclic secondary diamines such as piperazine and dipiperidylpropane; and heterocyclic tertiary diamines such as N,N-dimethylpiperazine and bismethylpiperidylpropane. The number of carbon atoms in the alicyclic amine and heterocyclic amine is preferably 3 or more, more preferably 4 or more, and the upper limit is preferably 16 or less, more preferably 14 or less.

[0054] Representative and preferred examples of the aromatic amine include aromatic primary diamines such as phenyldiamine, tolylenediamine, and naphthalenediamine; aromatic secondary diamines such as N-methylphenylenediamine, N,N'-dimethylphenylenediamine, N,N'-bismethylphenylphenylenediamine, N,N'-dimethylnaphthalenediamine, and N-naphthylethylenediamine; and aromatic tertiary diamines such as N,N-dimethylphenylenediamine, N,N,N',N'-tetramethylphenylenediamine, N,N,N',N'-tetramethyldiaminodiphenylmethane, and N,N,N',N'-tetramethylnaphthalenediamine. The aromatic amine has preferably 6 or more, more preferably 7 or more, and even more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and even more preferably 12 or less.

[0055] The amine compound used in the present embodiment may be substituted with a substituent such as an alkyl group, an alkenyl group, an alkoxyl group, a hydroxyl group, or a cyano group, or with a halogen atom. Although diamines have been given as specific examples, it goes without saying that the amine compounds that can be used in this embodiment are not limited to diamines, and examples thereof include aliphatic monoamines corresponding to various diamines such as trimethylamine, triethylamine, ethyldimethylamine, and the above-mentioned aliphatic diamines, piperidine compounds such as piperidine, methylpiperidine, and tetramethylpiperidine, pyridine compounds such as pyridine and picoline, morpholine compounds such as morpholine, methylmorpholine, and thiomorpholine, imidazole compounds such as imidazole and methylimidazole, and the above-mentioned alicyclic diamines. In addition to monoamines such as alicyclic monoamines such as the corresponding monoamines, heterocyclic monoamines corresponding to the above heterocyclic diamines, and aromatic monoamines corresponding to the above aromatic diamines, polyamines having three or more amino groups, such as diethylenetriamine, N,N',N''-trimethyldiethylenetriamine, N,N,N',N'',N''-pentamethyldiethylenetriamine, triethylenetetramine, N,N'-bis[(dimethylamino)ethyl]-N,N'-dimethylethylenediamine, hexamethylenetetramine, and tetraethylenepentamine, can also be used.

[0056] Among the above, from the viewpoint of obtaining higher ion conductivity, a tertiary amine having a tertiary amino group as an amino group is preferable, a tertiary diamine having two tertiary amino groups is more preferable, a tertiary diamine having two tertiary amino groups at both ends is even more preferable, and an aliphatic tertiary diamine having a tertiary amino group at both ends is even more preferable. In the above amine compounds, the aliphatic tertiary diamine having a tertiary amino group at both ends is preferably tetramethylethylenediamine, tetraethylethylenediamine, tetramethyldiaminopropane, or tetraethyldiaminopropane, and considering the ease of availability, etc., tetramethylethylenediamine or tetramethyldiaminopropane is preferable.

[0057] As a complexing agent other than the amine compounds, for example, a compound having a group containing a heteroatom such as an oxygen atom or a halogen atom such as a chlorine atom has a high affinity with lithium atoms and can be mentioned as a complexing agent other than the above amine compounds. In addition, a compound having a group other than an amino group, such as a nitro group or an amide group, containing a nitrogen atom as a heteroatom can also provide the same effect.

[0058] Compounds not having nitrogen atoms can also be used as the above-mentioned other complexing agents. For example, alcohol-based solvents such as ethanol and butanol, ester-based solvents such as ethyl acetate and butyl acetate, aldehyde-based solvents such as formaldehyde, acetaldehyde, and dimethylformamide, ketone-based solvents such as acetone and methyl ethyl ketone, ether-based solvents described below, halogen-containing aromatic hydrocarbon solvents such as trifluoromethylbenzene, nitrobenzene, chlorobenzene, chlorotoluene, and bromobenzene, and solvents containing carbon atoms and heteroatoms such as acetonitrile, dimethyl sulfoxide, and carbon disulfide can be mentioned. Among these, ether-based solvents are preferred, and examples thereof include ether compounds such as aliphatic ethers, alicyclic ethers, heterocyclic ethers, aromatic ethers, etc. The molecule may have one or more ether bonds, and from the viewpoint of the strength of the coordinate bond with a lithium atom or the like, glycol-based solvents having two or more ether bonds are preferred.

[0059] More specifically, diethyl ether, diisopropyl ether, dibutyl ether, tetrahydrofuran, dimethoxyethane, cyclopentyl methyl ether, tert-butyl methyl ether, anisole, dimethoxyethane (DME), diethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol diethyl ether, and triethylene glycol dimethyl ether are more preferable, and dimethoxyethane (DME) is even more preferable.

[0060] As the solvent other than the amine compound, for example, a compound having a group containing a heteroatom such as an oxygen atom or a halogen atom such as a chlorine atom has a high affinity with lithium atoms, and can be cited as a complexing agent other than the above amine compound. In addition, a compound having a group other than an amino group, such as a nitro group or an amide group, containing a nitrogen atom as a heteroatom can also obtain the same effect. However, in the manufacturing method of the present embodiment, a complexing agent other than the amine compound functions as a complexing agent when used alone, but when used in combination with an amine compound, the amine compound predominantly functions as the complexing agent described above, so that the complexing agent does not substantially function as a complexing agent, and can function as a solvent described later.

[0061] Some of these solvents, for example, ether solvents having a heteroatom, can also be used as the solvent described below. As described above, when an amine compound is used as a complexing agent, the amine compound predominantly functions as the complexing agent described above, and therefore solvents other than the amine compound do not substantially function as a complexing agent and may function as a solvent. The ether solvents listed as other complexing agents can function as a solvent when an amine compound is used as a complexing agent, and can function as a complexing agent when an amine compound is not used. Therefore, the ether solvents are also listed as examples of other solvents.

[0062] When a solvent is used, the content of the polar solvent relative to the total amount of the complexing agent and the solvent is preferably 10 mass% or more, more preferably 15 mass% or more, and even more preferably 20 mass% or more, and the upper limit is preferably 65 mass% or less, more preferably 60 mass% or less, and even more preferably 55 mass% or less.

[0063] (Method of producing sulfides) The sulfide can be produced by mixing the raw materials for the sulfide. The mixing can be performed in the same manner as described above.

[0064] (Method of preparing complex (1)) The complex (1) can be prepared by mixing the above-mentioned sulfide with the complexing agent (1). The mixing can be carried out in the same manner as the above-mentioned mixing method.

[0065] <Complex (2)> The complex (2) of the present embodiment must contain a lithium atom and a halogen atom as constituent elements, and preferably further contains a complexing agent (2) described below as a constituent element. These may be used alone or in combination of two or more. When two or more kinds are used in combination, a halogenated complex may be prepared from a plurality of halides and a complexing agent (2). However, it is more preferable to prepare a halogenated complex A from one kind of halide A and a complexing agent (2), prepare a halogenated complex B using another kind of halide B, and mix these to prepare a halogenated complex.

[0066] The content of the complexing agent (2) in the complex (2) is preferably 20 mass % or more, more preferably 30 mass % or more, and even more preferably 40 mass % or more, based on the total amount of the complex (2), from the viewpoint of obtaining a sulfide solid electrolyte having high ionic conductivity, and is preferably 90 mass % or less, more preferably 85 mass % or less, and even more preferably 80 mass % or less, from the viewpoint of crystal formation.

[0067] (Halides) The halide contains lithium atoms and halogen atoms, and from the viewpoint of obtaining a sulfide solid electrolyte having high ionic conductivity, the raw material of the halide is preferably a lithium halide such as lithium chloride (LiCl), lithium bromide (LiBr), or lithium iodide (LiI). When two or more types of complex (2) are used in combination, a combination of lithium chloride and lithium bromide or a combination of lithium bromide and lithium iodide is preferred, and a combination of lithium bromide and lithium iodide is more preferred.

[0068] When a lithium bromide complex and a lithium iodide complex are used in combination, from the viewpoint of improving ionic conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium iodide excluding the complex in the complex is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, further preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%. In addition, lithium compounds such as lithium oxide, lithium hydroxide, and lithium carbonate; alkali metal sulfides such as sodium sulfide, potassium sulfide, rubidium sulfide, and cesium sulfide; metal sulfides such as silicon sulfide, germanium sulfide, boron sulfide, gallium sulfide, tin sulfide (SnS, SnS2), aluminum sulfide, and zinc sulfide; phosphate compounds such as sodium phosphate and lithium phosphate; halides of alkali metals other than lithium, such as sodium iodide, sodium fluoride, sodium chloride, and sodium bromide; metal halides such as aluminum halides, silicon halides, germanium halides, arsenic halides, selenium halides, tin halides, antimony halides, tellurium halides, and bismuth halides; phosphorus oxyhalides such as phosphorus oxychloride (POCl3) and phosphorus oxybromide (POBr3); and the like may be used. The same applies to the complex (2) described above.

[0069] (Complexing Agent (2)) The complexing agent (2) is as described above with respect to the complexing agent (1). The complexing agent (2) may be the same as or different from the complexing agent (1).

[0070] (Method of producing halides) The halide can be prepared by mixing the above-mentioned halide raw materials. The mixing can be carried out in the same manner as described above.

[0071] (Method of preparing halide complexes) The halide complex can be prepared by mixing the above-mentioned halide with the complexing agent (2) in the same manner as described above.

[0072] <Complex (1) and Complex (2)> This embodiment requires mixing complex (1) and complex (2). The amounts of complex (1) and complex (2) used depend on the types of complex (1) and complex (2) used and cannot be generalized; however, when a Li3PS4 complex prepared from lithium sulfide and diphosphorus pentasulfide is used as complex (1) and a lithium bromide complex and a lithium iodide complex are used as complex (2), the ratio of lithium bromide and lithium iodide to Li3PS4 before complexation is preferably 30 to 70 mol%, more preferably 35 to 65 mol%, and even more preferably 40 to 60 mol%, from the viewpoint of improving ionic conductivity.

[0073] (solvent) It is preferable to add a solvent when mixing the sulfide and the complexing agent (1), when mixing the halide and the complexing agent (2), and when mixing the complex (1) and the complex (2). By mixing the sulfide and the complexing agent (1) using a solvent, and mixing the halide and the complexing agent (2), the formation of the complex (1) and the complex (2) is promoted. Furthermore, by mixing the complex (1) and the complex (2) using a solvent, the formation of the precursor is promoted, and it becomes easier to make the lithium-containing complex (1) such as the PS4 structure and the lithium-containing complex (2) such as the lithium halide exist evenly. This makes it possible to obtain a precursor in which the halogen atoms are more dispersed and fixed, which makes it easier to achieve the effect of obtaining high ionic conductivity.

[0074] Preferred examples of solvents having such properties include solvents having a solubility parameter of 10 or less. In this specification, the solubility parameter is a value δ ((cal / cm) calculated by the following formula (1) as described in various documents, such as "Chemical Handbook" (published in 2004, revised 5th edition, Maruzen Co., Ltd.). 3 ) 1 / 2 ) and is also called the Hildebrand parameter or SP value.

[0075]

number

[0076] By using a solvent with a solubility parameter of 10 or less, the solvent has a property of being relatively difficult to dissolve halogen atoms, raw materials containing halogen atoms such as lithium halide, and further components containing halogen atoms constituting the cocrystal contained in the precursor (for example, an aggregate in which lithium halide and a complexing agent are bonded), etc., compared to the above complexing agent, and the halogen atoms are easily fixed in the precursor, and the halogen atoms are present in a well-dispersed state in the obtained precursor and further in the sulfide solid electrolyte, making it easier to obtain a sulfide solid electrolyte having high ion conductivity. That is, it is preferable that the solvent used in this embodiment has a property of not dissolving the precursor. From the same viewpoint, the solubility parameter of the solvent is preferably 9.5 or less, more preferably 9.0 or less, and even more preferably 8.5 or less.

[0077] More specifically, the solvent used in the method for producing a sulfide solid electrolyte can be a wide variety of solvents that have been conventionally used in the production of sulfide solid electrolytes. Examples of the solvent include hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents; solvents containing carbon atoms such as alcohol-based solvents, ester-based solvents, aldehyde-based solvents, ketone-based solvents, ether-based solvents, and solvents containing carbon atoms and heteroatoms; and the like. Of these, a solvent may be appropriately selected from those preferably having a solubility parameter in the above-mentioned range, and at least one solvent selected from aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, and ether-based solvents is preferred.

[0078] More specifically, aliphatic hydrocarbon solvents such as hexane (7.3), pentane (7.0), 2-ethylhexane, heptane (7.4), octane (7.5), decane, undecane, dodecane, and tridecane; alicyclic hydrocarbon solvents such as cyclohexane (8.2) and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene (8.8), xylene (8.8), mesitylene, ethylbenzene (8.8), tert-butylbenzene, trifluoromethylbenzene, nitrobenzene, chlorobenzene (9.5), chlorotoluene (8.8), and bromobenzene; alcoholic solvents such as ethanol (12.7) and butanol (11.4); and acetic acid. Examples of solvents include ester solvents such as ethyl acetate (9.1) and butyl acetate (8.5); aldehyde solvents such as formaldehyde, acetaldehyde (10.3), and dimethylformamide (12.1); ketone solvents such as acetone (9.9) and methyl ethyl ketone; ether solvents such as diethyl ether (7.4), diisopropyl ether (6.9), dibutyl ether, tetrahydrofuran (9.1), dimethoxyethane (7.3), cyclopentyl methyl ether (8.4), tert-butyl methyl ether, and anisole; and solvents containing carbon atoms and heteroatoms such as acetonitrile (11.9), dimethyl sulfoxide, and carbon disulfide. The numbers in parentheses in the above examples are SP values.

[0079] Among these solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, and ether-based solvents are preferred, and from the viewpoint of obtaining a more stable and high ion conductivity, heptane, cyclohexane, toluene, ethylbenzene, diethyl ether, diisopropyl ether, dibutyl ether, dimethoxyethane, cyclopentyl methyl ether, tert-butyl methyl ether, and anisole are more preferred, diethyl ether, diisopropyl ether, and dibutyl ether are even more preferred, and diisopropyl ether and dibutyl ether are even more preferred, and dibutyl ether is particularly preferred. The solvent used in this embodiment is preferably the organic solvent exemplified above, and is an organic solvent different from the complexing agent. In this embodiment, these solvents may be used alone or in combination.

[0080] When a solvent is used, the amount of the solvent used is preferably 5 to 50 mL, and more preferably 10 to 30 mL, per 1 g of the total mass of complex (1) and complex (2).

[0081] <Precursor> As described above, the precursor is obtained by mixing the complex (1) containing the sulfide containing a sulfur atom and a phosphorus atom as a component, and the complex (2) containing the halide containing a lithium atom and a halogen atom as a component. The precursor contains a complexing agent, a lithium atom, a sulfur atom, a phosphorus atom, and a halogen atom as components. By obtaining a precursor, the sulfide solid electrolyte becomes a more uniform solid electrolyte with more dispersed halogen atoms and has high ionic conductivity, which is preferable. Here, the complexing agent contained in the precursor is derived from the complexing agent (1) and the complexing agent (2).

[0082] The precursor is also characterized by having a structure different from that of the sulfide solid electrolyte. This is specifically confirmed in the Examples. Figure 9 also shows the X-ray diffraction pattern of the sulfide solid electrolyte obtained in the Examples, which is different from the diffraction pattern of the precursor (Figure 8).

[0083] The precursor is preferably in the form of a co-crystal. The cocrystal is composed of a complexing agent, a lithium atom, a sulfur atom, a phosphorus atom, and a halogen atom, and is typically presumed to form a complex structure in which the lithium atom is directly bonded to other atoms with and / or without the intervention of a complexing agent.

[0084] In the method for producing a solid electrolyte according to the present embodiment, it is preferable to form a co-crystal containing halogen atoms in terms of improving ionic conductivity. By using a complexing agent, a lithium-containing structure such as a PS4 structure and a lithium-containing raw material such as lithium halide are bonded (coordinated) via the complexing agent, and it becomes easier to obtain a co-crystal in which halogen atoms are more dispersed and fixed, thereby improving ionic conductivity. Here, the fact that the precursor constitutes a cocrystal can be confirmed by, for example, gas chromatography analysis. Specifically, the precursor powder is dissolved in methanol, and the resulting methanol solution is analyzed by gas chromatography to quantitatively determine the amount of the complexing agent contained in the cocrystal.

[0085] The fact that the halogen atoms in the precursor form a co-crystal can be confirmed by the fact that a predetermined amount of halogen atoms is contained in the precursor even after solid-liquid separation of the precursor-containing material. This is because halogen atoms that do not form a co-crystal are more easily dissolved than halogen atoms that form a co-crystal and are discharged into the liquid of solid-liquid separation. It can also be confirmed by the fact that the proportion of halogen atoms in the precursor or sulfide solid electrolyte is not significantly reduced compared to the proportion of halogen atoms supplied from the raw material, by composition analysis of the precursor or sulfide solid electrolyte using ICP analysis (inductively coupled plasma atomic emission spectroscopy). The amount of halogen atoms remaining in the precursor is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more, based on the charged composition. The upper limit of the amount of halogen atoms remaining in the precursor is 100% by mass.

[0086] The content of the complexing agent (complexing agent (1) and complexing agent (2)) in the precursor is preferably 30 mass % or more, more preferably 35 mass % or more, and even more preferably 40 mass % or more, based on the total amount of the precursor, from the viewpoint of obtaining a solid electrolyte having high ion conductivity, and is preferably 90 mass % or less, more preferably 80 mass % or less, and even more preferably 70 mass % or less, from the viewpoint of crystal formation.

[0087] (Crushing) The method for producing the sulfide solid electrolyte of the present embodiment preferably further includes pulverizing the sulfide, halide, precursor, and / or sulfide solid electrolyte. By pulverizing the sulfide, halide, precursor, and / or sulfide solid electrolyte, a sulfide solid electrolyte having a small particle size can be obtained while suppressing a decrease in ion conductivity. The pulverizer used for pulverization in this embodiment is not particularly limited as long as it can pulverize particles, and for example, a media-type pulverizer using a pulverizing medium can be used. Among the media-type pulverizers, a wet pulverizer that can handle wet pulverization is preferable, considering that the precursor is mainly in a liquid state accompanied by liquids such as a complexing agent and a solvent, or in a slurry state. Representative examples of wet grinding machines include wet bead mills, wet ball mills, and wet vibration mills, among which wet bead mills using beads as grinding media are preferred because they allow the grinding conditions to be freely adjusted and are easy to handle smaller particle sizes. Dry grinding machines such as dry media grinding machines such as dry bead mills, dry ball mills, and dry vibration mills, and dry non-media grinding machines such as jet mills can also be used.

[0088] In addition, when the precursor to be pulverized by the pulverizer is in a slurry state, it is preferable to use a flow-type pulverizer that can perform a circulation operation to circulate the precursor as necessary. More specifically, it is preferable to use a pulverizer that circulates the slurry between a pulverizer (pulverizing mixer) that pulverizes the slurry and a temperature holding tank (reaction vessel), as described in JP-A-2010-140893.

[0089] The size of the beads used in the above-mentioned grinding machine may be appropriately selected depending on the desired particle size, processing amount, etc. For example, the diameter of the beads may be about 0.05 mmφ or more and 5.0 mmφ or less, preferably 0.1 mmφ or more and 3.0 mmφ or less, and more preferably 0.3 mmφ or more and 2.5 mmφ or less.

[0090] As a grinding machine used for grinding the sulfide, halide, precursor and / or sulfide solid electrolyte, a machine capable of grinding an object using ultrasound, for example, a machine called an ultrasonic grinder, ultrasonic homogenizer, probe ultrasonic grinder, etc., can be used. In this case, various conditions such as the frequency of the ultrasonic waves may be appropriately selected depending on the average particle size of the desired precursor, and the frequency may be, for example, about 1 kHz or more and 100 kHz or less, and from the viewpoint of more efficiently pulverizing the precursor, the frequency is preferably 3 kHz or more and 50 kHz or less, more preferably 5 kHz or more and 40 kHz or less, and even more preferably 10 kHz or more and 30 kHz or less. The output of the ultrasonic crusher may usually be about 500 to 16,000W, preferably 600 to 10,000W, more preferably 750 to 5,000W, and further preferably 900 to 1,500W.

[0091] The average particle size (D 50 ) is appropriately determined according to the desire, but is usually 0.01 μm or more and 50 μm or less, preferably 0.03 μm or more and 5 μm or less, and more preferably 0.05 μm or more and 3 μm or less. By setting the average particle size in this range, it is possible to meet the demand for a sulfide solid electrolyte having a small particle size of 1 μm or less.

[0092] The grinding time is not particularly limited as long as it is a time that allows the sulfide, halide, precursor and / or sulfide solid electrolyte to have a desired average particle size, and is usually from 0.1 hours to 100 hours. From the viewpoint of efficiently achieving a desired particle size, the grinding time is preferably from 0.3 hours to 72 hours, more preferably from 0.5 hours to 48 hours, and even more preferably from 1 hour to 24 hours.

[0093] The pulverization may be carried out after drying the sulfide, halide, precursor and / or sulfide solid electrolyte and converting the precursor into a powder. In this case, it is preferable to use any of the dry grinders among the grinders given above as examples of grinders that can be used in the present production method.

[0094] (Dry) The method for producing the sulfide solid electrolyte of this embodiment may include drying the complex (1), the complex (2), the precursor, and / or the sulfide solid electrolyte. This removes the complexing agent, the solvent, and the like, and a powder of the complex (1), the complex (2), the precursor, and / or the sulfide solid electrolyte is obtained. By drying in advance, heating can be performed efficiently. Note that drying and the subsequent heating may be performed in the same step.

[0095] The drying can be performed at a temperature according to the type of the solvent or the remaining complexing agent (complexing agent not incorporated in the material to be dried) of the complex (1), complex (2), precursor, and / or sulfide solid electrolyte. For example, the drying can be performed at a temperature equal to or higher than the boiling point of the solvent or complexing agent. The drying can be performed by drying under reduced pressure (vacuum drying) using a vacuum pump or the like at a temperature of usually 5 to 100°C, preferably 10 to 85°C, more preferably 15 to 70°C, and even more preferably about room temperature (23°C) (for example, about room temperature ±5°C) to volatilize the complexing agent.

[0096] The drying may be performed by filtering the complex (1), the complex (2), the precursor, and / or the sulfide solid electrolyte using a glass filter or the like, subjecting the complex (1), the complex (2), the precursor, and / or the sulfide solid electrolyte to solid-liquid separation by decantation, or subjecting the complex (1), the complex (2), the precursor, and / or the sulfide solid electrolyte to solid-liquid separation using a centrifuge, etc. In this embodiment, after the solid-liquid separation, the complex (1), the complex (2), the precursor, and / or the sulfide solid electrolyte may be dried under the above-mentioned temperature conditions. Specifically, the solid-liquid separation can be easily carried out by decantation, which removes the complexing agent and the solvent that become the supernatant after precipitation of Complex (1), Complex (2), the precursor and / or the sulfide solid electrolyte, or by filtration using a glass filter having a pore size of about 10 to 200 μm, preferably 20 to 150 μm.

[0097] (heating) The method for producing the sulfide solid electrolyte of the present embodiment preferably further includes heating after mixing the complex (1) and the complex (2). That is, the method preferably includes heating the precursor to obtain an amorphous sulfide solid electrolyte, or heating the precursor or the amorphous sulfide solid electrolyte to obtain a crystalline sulfide solid electrolyte. By including heating the precursor, the complexing agent, the solvent, and the like in the precursor are removed, and an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms is obtained. The precursor heated by this heating may be a pulverized product of the precursor pulverized by the above-mentioned pulverization.

[0098] Here, the removal of the complexing agent in the precursor is supported by the fact that it is clear from the results of X-ray diffraction patterns, gas chromatography analysis, etc. that the complexing agent forms a co-crystal with the precursor, and in addition, the X-ray diffraction pattern of the sulfide solid electrolyte obtained by removing the complexing agent by heating the precursor is the same as that of the sulfide solid electrolyte obtained by a conventional method without using a complexing agent.

[0099] In the manufacturing method of the present embodiment, the sulfide solid electrolyte is obtained by removing the complexing agent from the precursor by heating the precursor, and the less the complexing agent in the sulfide solid electrolyte, the better, but the complexing agent may be contained to an extent that does not impair the performance of the sulfide solid electrolyte. The content of the complexing agent in the sulfide solid electrolyte is usually 10 mass % or less, preferably 5 mass % or less, more preferably 3 mass % or less, and further preferably 1 mass % or less.

[0100] In the manufacturing method of this embodiment, a crystalline sulfide solid electrolyte may be obtained by heating a precursor, or a precursor may be heated to obtain an amorphous sulfide solid electrolyte, and then the amorphous sulfide solid electrolyte may be heated. That is, in the manufacturing method of this embodiment, an amorphous sulfide solid electrolyte can also be produced. Conventionally, in order to obtain a crystalline sulfide solid electrolyte having high ionic conductivity, for example, a sulfide solid electrolyte having a thiolicon region II type crystal structure described later, it was necessary to prepare an amorphous sulfide solid electrolyte by mechanical pulverization such as mechanical milling, or other melt quenching treatments, and then heat the amorphous sulfide solid electrolyte to obtain it. However, the manufacturing method of this embodiment is superior to the conventional manufacturing method by mechanical milling, etc., in that a crystalline sulfide solid electrolyte having a thiolicon region II type crystal structure can be obtained by a method that does not involve mechanical pulverization or other melt quenching treatments.

[0101] In the method for producing the sulfide solid electrolyte of the present embodiment, whether to obtain an amorphous sulfide solid electrolyte, a crystalline sulfide solid electrolyte, or even to obtain a crystalline sulfide solid electrolyte after obtaining an amorphous sulfide solid electrolyte, or to obtain a crystalline sulfide solid electrolyte directly from a precursor is appropriately selected as desired, and can be adjusted by the heating temperature, heating time, etc. The heating temperature of the precursor may be determined according to the structure of the crystalline sulfide solid electrolyte obtained by heating the amorphous sulfide solid electrolyte (or precursor), for example, when obtaining an amorphous sulfide solid electrolyte. Specifically, the amorphous sulfide solid electrolyte (or precursor) is subjected to differential thermal analysis (DTA) at a temperature rise rate of 10 ° C. / min using a differential thermal analyzer (DTA device), and the heating temperature is preferably set to 5 ° C. or less, more preferably 10 ° C. or less, and even more preferably 20 ° C. or less, starting from the temperature of the top of the exothermic peak observed on the lowest temperature side. There is no particular limit to the lower limit, but it may be set to about −40 ° C. or more, which is the peak top temperature of the exothermic peak observed on the lowest temperature side. By setting the temperature range, an amorphous sulfide solid electrolyte can be obtained more efficiently and reliably.

[0102] The heating temperature for obtaining an amorphous sulfide solid electrolyte cannot be generally defined because it varies depending on the structure of the crystalline sulfide solid electrolyte to be obtained. However, it is usually preferably 250° C. or lower, more preferably 220° C. or lower, and even more preferably 200° C. or lower. There is no particular lower limit, but it is preferably 90° C. or higher, more preferably 100° C. or higher, and even more preferably 110° C. or higher.

[0103] In addition, the heating is preferably carried out under reduced pressure, preferably 0.1 Pa or more from the viewpoint of the apparatus, more preferably 1.0 Pa or more, and even more preferably 5.0 Pa or more, and from the viewpoint of obtaining a solid electrolyte having high ionic conductivity. It is preferably 100.0 Pa or less, more preferably 50.0 Pa or less, and even more preferably 20.0 Pa or less.

[0104] In addition, when the amorphous sulfide solid electrolyte is heated or the crystalline sulfide solid electrolyte is obtained directly from the precursor, the heating temperature may be determined according to the structure of the crystalline sulfide solid electrolyte, and is preferably higher than the heating temperature for obtaining the amorphous sulfide solid electrolyte. Specifically, the amorphous sulfide solid electrolyte (or precursor) is subjected to differential thermal analysis (DTA) at a temperature rise of 10 ° C. / min using a differential thermal analyzer (DTA device), and the temperature is preferably 5 ° C. or higher, more preferably 10 ° C. or higher, and even more preferably 20 ° C. or higher, starting from the peak top temperature of the exothermic peak observed on the lowest temperature side. There is no particular limit to the upper limit, but it may be about 40 ° C. or lower. By setting the temperature range, the crystalline sulfide solid electrolyte can be obtained more efficiently and reliably. The heating temperature for obtaining a crystalline sulfide solid electrolyte cannot be generally defined because it varies depending on the structure of the crystalline sulfide solid electrolyte to be obtained. Generally, however, it is preferably 130°C or higher, more preferably 135°C or higher, and even more preferably 140°C or higher. There is no particular upper limit, but it is preferably 300°C or lower, more preferably 280°C or lower, and even more preferably 250°C or lower.

[0105] The heating time is not particularly limited as long as the desired amorphous sulfide solid electrolyte or crystalline sulfide solid electrolyte can be obtained, but is preferably, for example, 1 minute or more, more preferably 10 minutes or more, even more preferably 30 minutes or more, and even more preferably 1 hour or more. The upper limit of the heating time is not particularly limited, but is preferably 24 hours or less, more preferably 10 hours or less, even more preferably 5 hours or less, and even more preferably 3 hours or less.

[0106] Moreover, the heating is preferably performed in an inert gas atmosphere (e.g., nitrogen atmosphere, argon atmosphere) or reduced pressure atmosphere (particularly in vacuum). This is because deterioration (e.g., oxidation) of the crystalline sulfide solid electrolyte can be prevented. The heating method is not particularly limited, and examples thereof include a method using a hot plate, a vacuum heating device, an argon gas atmosphere furnace, and a baking furnace. Furthermore, industrially, a horizontal dryer having a heating means and a feeding mechanism, a horizontal vibration fluidized dryer, etc. can also be used, and may be selected according to the amount of processing to be heated.

[0107] (Amorphous sulfide solid electrolyte) The amorphous sulfide solid electrolyte obtained by the method for producing a sulfide solid electrolyte of this embodiment contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms. Representative examples include sulfide solid electrolytes composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, and Li2S-P2S5-LiI-LiBr; and sulfide solid electrolytes further containing other atoms such as oxygen atoms and silicon atoms, such as Li2S-P2S5-Li2O-LiI and Li2S-SiS2-P2S5-LiI. From the viewpoint of obtaining higher ionic conductivity, a sulfide solid electrolyte composed of lithium sulfide, phosphorus sulfide, and lithium halide, such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, or Li2S-P2S5-LiI-LiBr, is preferred. The types of atoms constituting the amorphous sulfide solid electrolyte can be confirmed, for example, by an ICP emission spectroscopic analyzer.

[0108] When the amorphous sulfide solid electrolyte obtained by the method for producing a sulfide solid electrolyte of this embodiment contains at least Li2S-P2S5, the molar ratio of Li2S to P2S5 is preferably 65-85:15-35, more preferably 70-80:20-30, and even more preferably 72-78:22-28, from the viewpoint of obtaining higher ionic conductivity. In the case where the amorphous sulfide solid electrolyte obtained by the method for producing a sulfide solid electrolyte of the present embodiment is, for example, Li2S-P2S5-LiI-LiBr, the total content of lithium sulfide and diphosphorus pentasulfide is preferably 60 to 95 mol%, more preferably 65 to 90 mol%, and even more preferably 70 to 85 mol%. The ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, even more preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%.

[0109] In the amorphous sulfide solid electrolyte obtained by the method for producing a sulfide solid electrolyte of the present embodiment, the compounding ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms is preferably 1.0-1.8:1.0-2.0:0.1-0.8:0.01-0.6, more preferably 1.1-1.7:1.2-1.8:0.2-0.6:0.05-0.5, and still more preferably 1.2-1.6:1.3-1.7:0.25-0.5:0.08-0.4. Furthermore, when bromine and iodine are used in combination as halogen atoms, the compounding ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms, bromine, and iodine is preferably 1.0-1.8:1.0-2.0:0.1-0.8:0.01-0.3:0.01-0.3, more preferably 1.1-1.7:1.2-1.8:0.2-0.6:0.02-0.25:0.02-0.25, more preferably 1.2-1.6:1.3-1.7:0.25-0.5:0.03-0.2:0.03-0.2, and even more preferably 1.35-1.45:1.4-1.7:0.3-0.45:0.04-0.18:0.04-0.18. By setting the compounding ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms within the above range, it becomes easier to obtain a sulfide solid electrolyte having a higher ionic conductivity and a thiolithium region II type crystal structure described later.

[0110] The shape of the amorphous sulfide solid electrolyte is not particularly limited, but may be, for example, particulate. The average particle diameter (D 50) can be, for example, in the range of 0.01 μm to 500 μm, or 0.1 to 200 μm.

[0111] (Crystalline sulfide solid electrolyte) The crystalline sulfide solid electrolyte obtained by the method for producing a sulfide solid electrolyte of the present embodiment may be a so-called glass ceramic obtained by heating an amorphous sulfide solid electrolyte to a crystallization temperature or higher. Examples of the crystal structure include a Li3PS4 crystal structure, a Li4P2S6 crystal structure, a Li7PS6 crystal structure, a Li7P3S 11 Examples of such structures include a crystal structure having peaks at 2θ=approximately 20.2° and 23.6° (for example, JP 2013-16423 A).

[0112] Also, Li 4-x Ge 1-x P x S4 thio-LISICON Region II crystal structure (Kanno et al., Journal of The Electrochemical Society, 148(7)A742-746(2001)), Li 4-x Ge 1-x P x Examples of the crystal structure include a crystal structure similar to the S4-based thio-LISICON Region II type (see Solid State Ionics, 177 (2006), 2721-2725). The crystal structure of the crystalline sulfide solid electrolyte obtained by the method for producing a sulfide solid electrolyte of the present embodiment is preferably the thio-LISICON Region II type crystal structure among the above, since it provides higher ionic conductivity.

[0113] Here, the "thiolicon region II type crystal structure" refers to Li 4-x Ge 1-x P x S4 thio-LISICON Region II crystal structure, Li 4-x Ge 1-x P xIt indicates that the crystalline structure is either similar to the S4-based thio-LISICON Region II type. The crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment may have the above-mentioned thio-LISICON Region II type crystal structure or may have it as the main crystal, but from the viewpoint of obtaining higher ionic conductivity, it is preferable that it has it as the main crystal. In this specification, "having it as the main crystal" means that the ratio of the target crystal structure among the crystal structures is 80% or more, preferably 90% or more, and more preferably 95% or more. In addition, it is preferable that the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment does not contain crystalline Li3PS4 (β-Li3PS4) from the viewpoint of obtaining higher ionic conductivity.

[0114] In X-ray diffraction measurements using CuKα radiation, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ = 17.5°, 18.3°, 26.1°, 27.3°, and 30.0°, the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ = 16.9°, 27.1°, and 32.5°, the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ = 15.3°, 25.2°, 29.6°, and 31.0°, and the diffraction peaks of the Li7P3S 11 Diffraction peaks of the crystal structure appear, for example, at 2θ = 17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°. 4-x Ge 1-x P x The diffraction peaks of the S4 thio-LISICON Region II crystal structure appear, for example, at 2θ = 20.1°, 23.9°, and 29.5°, and Li 4-x Ge 1-x P x Diffraction peaks of a crystal structure similar to the S4 thio-LISICON Region II type appear, for example, at 2θ=20.2 and 23.6°. Note that these peak positions may vary within a range of ±0.5°.

[0115] As described above, when a thio-Li3PS4 region II-type crystal structure is obtained in the present embodiment, it is preferably free of crystalline Li3PS4 (β-Li3PS4). X-ray diffraction measurement examples of the crystalline sulfide solid electrolyte obtained by the production method of the present embodiment are shown in FIGS. 9 to 11. The sulfide solid electrolyte of the present embodiment either does not have diffraction peaks at 2θ = 17.5° and 26.1° found in crystalline Li3PS4, or even if it has such peaks, the detected peaks are extremely small compared to the diffraction peaks of the thio-Li3PS4 region II-type crystal structure.

[0116] The crystal structure represented by the composition formula Li having the above-described structural framework of Li7PS6 and in which part of P is substituted with Si 7-x P 1-y Si y S6 and Li 7+x P 1-y Si y S6 (where x is -0.6 to 0.6 and y is 0.1 to 0.6) is cubic or orthorhombic, preferably cubic, and in X-ray diffraction measurement using CuKα rays, mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. The above composition formula Li 7-x-2y PS 6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5) is preferably cubic, and in X-ray diffraction measurement using CuKα rays, mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. Also, the above composition formula Li 7-x PS 6-x Ha x (where Ha is Cl or Br and x is preferably 0.2 to 1.8) is preferably cubic, and in X-ray diffraction measurement using CuKα rays, mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°. The positions of these peaks may vary within a range of ±0.5°.

[0117] The shape of the crystalline sulfide solid electrolyte is not particularly limited, but may be, for example, particulate. The average particle diameter (D 50 ) can be, for example, in the range of 0.01 μm to 500 μm, or 0.1 to 200 μm.

[0118] [Positive electrode mixture, negative electrode mixture] For example, when used in a positive electrode layer or a negative electrode layer, a positive electrode active material and a negative electrode active material are dispersed and mixed in a precursor-containing liquid or a precursor-containing slurry, which is a precursor-containing material, and then dried, so that the precursor adheres to the surface of the active material. Furthermore, as in the above embodiment, the precursor is heated to become an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte. At this time, by heating together with the active material, a positive electrode composite or a negative electrode composite in which the sulfide solid electrolyte adheres to the surface of the active material is obtained.

[0119] The positive electrode active material can be used without any particular limitation as long as it can promote the battery chemical reaction accompanied by the movement of lithium ions resulting from the lithium atoms preferably used as the atoms that exhibit ionic conductivity in this embodiment in relation to the negative electrode active material. Examples of such positive electrode active materials that can insert and remove lithium ions include oxide-based positive electrode active materials and sulfide-based positive electrode active materials.

[0120] Preferred examples of oxide-based positive electrode active materials include lithium-containing transition metal composite oxides such as LMO (lithium manganese oxide), LCO (lithium cobalt oxide), NMC (lithium nickel manganese cobalt oxide), NCA (lithium nickel cobalt aluminate), LNCO (lithium nickel cobalt oxide), and olivine-type compounds (LiMeNPO4, Me=Fe, Co, Ni, Mn). Examples of sulfide-based positive electrode active materials include titanium sulfide (TiS2), molybdenum sulfide (MoS2), iron sulfide (FeS, FeS2), copper sulfide (CuS), and nickel sulfide (Ni3S2). In addition to the above positive electrode active materials, niobium selenide (NbSe3) and the like can also be used. In this embodiment, the positive electrode active material may be used alone or in combination of two or more kinds.

[0121] As the negative electrode active material, any material that can promote a battery chemical reaction accompanied by the movement of lithium ions due to lithium atoms, such as an atom that is preferably used as an atom that exhibits ion conductivity in this embodiment, preferably a metal that can form an alloy with lithium atoms, an oxide thereof, an alloy of the metal and lithium atoms, etc., can be used without any particular limitation. As such a negative electrode active material capable of inserting and removing lithium ions, any material known as a negative electrode active material in the battery field can be used without any limitation. Examples of such negative electrode active materials include metallic lithium, metallic indium, metallic aluminum, metallic silicon, metallic tin, and other metallic lithium or metals capable of forming alloys with metallic lithium, oxides of these metals, and alloys of these metals with metallic lithium.

[0122] The electrode active material used in this embodiment may have a coating layer on its surface. The material for forming the coating layer may be an ion conductor such as a nitride, an oxide, or a composite of an atom, preferably a lithium atom, that exhibits ion conductivity in the crystalline sulfide solid electrolyte used in this embodiment. Specifically, lithium nitride (Li3N), Li4GeO4, or other ion conductors having a main structure, such as Li 4-2x Zinc x Conductors with a lithiated crystal structure such as GeO4, and conductors with a Li3PO4-type framework such as Li 4-x Ge 1-x P x Conductors with thiolicon-type crystal structures such as S4, La 2 / 3-x Li 3x Examples of such conductors include those having a perovskite crystal structure such as TiO3, and those having a NASICON crystal structure such as LiTi2(PO4)3.

[0123] Also, Li y Ti 3-y O4(0 <y<3)、Li4Ti5O 12 Examples of conductors include lithium titanates such as (LTO), lithium metal oxides of metals belonging to Group 5 of the periodic table such as LiNbO3 and LiTaO3, and oxide-based conductors such as Li2O-B2O3-P2O5, Li2O-B2O3-ZnO, and Li2O-Al2O3-SiO2-P2O5-TiO2.

[0124] An electrode active material having a coating layer can be obtained, for example, by applying a solution containing various atoms constituting the material that forms the coating layer to the surface of an electrode active material, and then calcining the electrode active material after application at a temperature of preferably 200°C or higher and 400°C or lower. Here, the solution containing various atoms may be a solution containing alkoxides of various metals such as lithium ethoxide, titanium isopropoxide, niobium isopropoxide, tantalum isopropoxide, etc. In this case, the solvent may be an alcohol solvent such as ethanol or butanol, an aliphatic hydrocarbon solvent such as hexane, heptane, or octane, or an aromatic hydrocarbon solvent such as benzene, toluene, or xylene. The above attachment may be performed by immersion, spray coating, or the like.

[0125] From the viewpoint of improving production efficiency and battery performance, the firing temperature is preferably from 200°C to 400°C, more preferably from 250°C to 390°C, and the firing time is usually from about 1 minute to 10 hours, preferably from 10 minutes to 4 hours.

[0126] The coverage of the coating layer is preferably 90% or more, more preferably 95% or more, and even more preferably 100% based on the surface area of ​​the electrode active material, that is, the entire surface is preferably covered. The thickness of the coating layer is preferably 1 nm or more, more preferably 2 nm or more, and the upper limit is preferably 30 nm or less, more preferably 25 nm or less. The thickness of the coating layer can be measured by cross-sectional observation using a transmission electron microscope (TEM), and the coverage can be calculated from the thickness of the coating layer, atomic analysis value, and BET surface area.

[0127] In addition, the battery preferably uses a current collector in addition to the positive electrode layer, the electrolyte layer, and the negative electrode layer, and a known current collector can be used. For example, a layer in which a material that reacts with the sulfide solid electrolyte, such as Au, Pt, Al, Ti, or Cu, is coated with Au or the like can be used. EXAMPLES

[0128] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these examples in any way.

[0129] (1) Describe the measurement method. (1-1) Volume-based average particle size (D50) The measurements were made using a laser diffraction / scattering particle size distribution analyzer (HORIBA, LA-950V2 model LA-950W2). A mixture of dehydrated toluene (Wako Pure Chemical Industries, special grade) and tertiary butyl alcohol (Wako Pure Chemical Industries, special grade) in a weight ratio of 93.8:6.2 was used as the dispersion medium. 50 mL of the dispersion medium was injected into the flow cell of the device and circulated, after which the measurement target was added and ultrasonicated, and the particle size distribution was measured. The amount of the measurement target was adjusted so that the red light transmittance (R) corresponding to the particle concentration on the measurement screen specified by the device was within 80 to 90% and the blue light transmittance (B) was within 70 to 90%. In addition, the calculation conditions used were 2.16 as the refractive index of the measurement target and 1.49 as the refractive index of the dispersion medium. In the distribution form setting, the number of repetitions was fixed at 15, and particle size calculation was performed.

[0130] (1-2) Ionic conductivity measurement The sulfide solid electrolyte produced in each example was filled into a tablet press, and a pressure of 22 MPa was applied to form a compact. Carbon was placed on both sides of the compact as electrodes, and pressure was applied again using the tablet press to produce a compact for measurement (diameter about 10 mm, thickness 0.1 to 0.2 cm). The ionic conductivity of this compact was measured by AC impedance measurement. The conductivity value was measured at 25°C.

[0131] (1-3) X-ray diffraction (XRD) measurement The resulting product was determined to be crystalline by XRD measurement. The powder of the precursor or solid electrolyte produced in each example was filled into a groove with a diameter of 20 mm and a depth of 0.2 mm, and the groove was smoothed with glass to prepare a sample. This sample was measured using a Kapton film for XRD without exposing it to air. The powder X-ray diffraction measurement was performed using a BRUKER Corporation D2 PHASER under the following conditions.

[0132] Tube voltage: 30kV Tube current: 10mA X-ray wavelength: Cu-Kα ray (1.5418Å) Optical system: Concentration method Slit configuration: Soller slit 4°, divergence slit 1mm, Kβ filter (Ni plate) Detector: Semiconductor detector Measurement range: 2θ=10-60deg Step width, scan speed: 0.05deg, 0.05deg / sec

[0133] (2) An example of the preparation of complex (1) (Li3PS4-TMEDA complex) is described. (2-1) Example of lithium sulfide (Li2S) production (2-1-1) Example of Li2S synthesis Toluene (Sumitomo Corporation), used as a non-aqueous medium, was dehydrated (measured with a Karl Fischer moisture meter and confirmed to have a moisture content of 100 ppm or less), and 303.8 kg of this was added to a 500 L (liter) stainless steel reaction kettle under a nitrogen stream. Subsequently, 33.8 kg of anhydrous lithium hydroxide (Honjo Chemical Co., Ltd.) was added, and the mixture was stirred at 131 rpm using a Twin Star stirring blade at 95°C for 2 hours to form a slurry.

[0134] While continuing stirring, hydrogen sulfide (Sumitomo Seika Chemicals Co., Ltd.) was blown into the slurry at a supply rate of 100 L / min, and the temperature was raised to 104°C. Azeotropic gas of water and toluene was continuously discharged from the reaction vessel. This azeotropic gas was dehydrated by condensing it in a condenser outside the system. During this time, toluene in an amount equal to the amount of toluene distilled was continuously supplied to keep the reaction liquid level constant. The amount of water in the condensate gradually decreased, and 24 hours after the introduction of hydrogen sulfide, no water was observed distilling out. During the reaction, the solid was dispersed in the toluene and stirred, and no water separated from the toluene.

[0135] Thereafter, the hydrogen sulfide was replaced with nitrogen and flowed at 100 L / min for 1 hour. The solid obtained was filtered and dried to obtain white powder Li2S, whose D50 was 412 μm.

[0136] (2-1-2) Pulverization of Li2S The Li2S obtained in (2-1-1) was pulverized in a pin mill equipped with a constant-volume feeder (100UPZ, manufactured by Hosokawa Micron Corporation) under a nitrogen atmosphere. The feeding rate was 80 g / min, and the disk rotation speed was 18,000 rpm. The D50 of the Li2S after the crushing process was 7.7 μm.

[0137] (2-2) Example of preparation of phosphorus pentasulfide (P2S5) (2-2-1) Crushing of P2S5 The same procedure was followed in (2-1-2) except that P2S5 (manufactured by Thermophos, D50=125 μm) was used in place of the Li2S obtained in (2-1-1). The D50 of P2S5 after the grinding process was 8.7 μm.

[0138] (2-3) Example of preparation of complex (1) (2-3-1) Example of preparation of Li3PS4-TMEDA complex (complex (1)) using N,N,N,N-tetramethylethane-1,2-diamine (TMEDA) as the complexing agent (1) In an inert gas atmosphere in a glove box, 10 g of Li2S obtained in (2-1-2) and P2S5 obtained in (2-2-1) were weighed in a Schlenk flask containing a stirrer so that the molar ratio was 3:1, and cooled with a mixture of acetone and liquid nitrogen. After cooling for 30 minutes, 100 mL of tetrahydrofuran (THF) was added under inert gas flow while stirring with a stirrer, and the mixture was stirred for another 3 days. The obtained slurry was filtered, and the obtained solid was washed with THF five times, and the solvent was dried in vacuum to obtain a Li3PS4-3THF complex. This complex was dried in vacuum at 90°C for 5 hours to obtain amorphous g-Li3PS4. 5 g of the g-Li3PS4 was weighed in a Schlenk flask containing a stirrer in an inert gas atmosphere in a glove box, and 20 mL of N,N,N,N-tetramethylethane-1,2-diamine (TMEDA) was added under inert gas flow and stirred. After reacting for 3 days, the solvent was dried in vacuum to obtain Li3PS4-TMEDA complex (complex (1)) (X-ray diffraction (XRD) spectrum is shown in Figure 2).

[0139] (2-3-2) Example of preparation of Li3PS4-DME complex (complex (1)) using dimethoxyethane (DME) as complexing agent (1) The Li3PS4-DME complex (complex (1)) was obtained in the same manner as in (2-3-1), except that 20 mL of dimethoxyethane (DME) was used instead of TMEDA.

[0140] (3) Example of preparation of complex (2) (3-1) Crushing of LiBr Grinding was carried out in the same manner as in (2-1-2), except that LiBr (manufactured by Honjo Chemical Co., Ltd., D50 = 38 μm) was used instead of Li2S obtained in (2-1-1). The D50 of the LiBr after the crushing treatment was 5.0 μm.

[0141] (3-2) Example of preparation of LiBr-TMEDA complex (complex (2)) using TMEDA as complexing agent (2) The LiBr-TMEDA complex (X-ray diffraction (XRD) spectrum is shown in FIG. 3) was obtained in the same manner as in (2-3), except that 5 g of LiBr obtained in (3-1) was used instead of g-Li3PS4.

[0142] (3-3) Pulverization of LiI Grinding was carried out in the same manner as in (2-1-2), except that LiI (Sigma-Aldrich, D50 = 308 μm) was used instead of Li2S obtained in (2-1-1). The D50 of the LiI after the pulverization treatment was 10.0 μm.

[0143] (3-4-1) Example of LiI-TMEDA complex (complex (2)) using TMEDA as complexing agent (2) A LiI-TMEDA complex (complex (2)) (X-ray diffraction (XRD) spectrum is shown in FIG. 4) was obtained in the same manner as in (2-3), except that 5 g of LiI obtained in (3-3) was used instead of Li2S and P2S5.

[0144] (3-4-2) Example of preparation of LiI-DME complex (complex (2)) using DME as complexing agent (2) LiI-DME (complex (2)) was obtained in the same manner as in (3-4-1), except that 20 mL of DME was used instead of TMEDA.

[0145] Example 1 The Li3PS4-TMEDA complex obtained in (2-3-1), the LiBr-TMEDA complex obtained in (3-2), and the LiI-TMEDA complex obtained in (3-4-1) were weighed out in total 2.0 g so that the molar ratio of Li3PS4:LiBr:LiI was 4:1:1, where the masses after weight loss by TG-DTA (Figures 5, 6, and 7) were the masses of Li3PS4, LiBr, and LiI, respectively. The resulting mixture was placed in a zirconia ball mill pot (Fritsch P-7) containing 34 g of zirconia balls with a diameter of 2 mm under an inert gas atmosphere in a glove box, and then placed in the zirconia ball mill pot together with 25 mL of dehydrated dibutyl ether (DBE FUJIFILM special grade), and then sealed under an inert gas atmosphere in a glove box. The zirconia ball mill was used for mixing at 200 rpm for 2 hours, and the solvent was vacuum dried to obtain precursor (1) (FIG. 8).

[0146] The obtained precursor (1) was weighed out in an amount of 1.5 g in a Schlenk flask under an inert gas atmosphere in a glove box, taken out of the glove box under an inert gas atmosphere, and heated at 180°C for 2 hours under a reduced pressure of 10 Pa or less to obtain a sulfide solid electrolyte (1). The XRD pattern of the sulfide solid electrolyte (1) is as shown in Figure 9, and it was confirmed that it contains a thiolicon region II type crystal structure. The ionic conductivity was 4.2 mS / cm.

[0147] Example 2 In a glove box, under an inert gas atmosphere, 2.0 g of each TMEDA complex was weighed out in a Schlenk flask containing a stirrer in the same manner as in Example 1, and 20 mL of dibutyl ether was added under an inert gas atmosphere and stirred for 3 days. Thereafter, the solvent was vacuum dried to obtain precursor (2).

[0148] The obtained precursor (2) was weighed out in an amount of 1.5 g in a Schlenk flask under an inert gas atmosphere in a glove box, taken out of the glove box under an inert gas atmosphere, and heated at 180°C for 2 hours under a reduced pressure of 10 Pa or less to obtain a sulfide solid electrolyte (2). The XRD pattern of the sulfide solid electrolyte (2) is as shown in Figure 9, and it was confirmed that it contains a thiolicon region II type crystal structure. The ionic conductivity was 3.5 mS / cm.

[0149] Example 3 In a glove box under an inert gas atmosphere, 2.0 g of each TMEDA complex was weighed out in a mortar in the same manner as in Example 1, and dry-mixed for 30 minutes under an inert gas atmosphere to obtain a precursor (3).

[0150] The obtained precursor (3) was weighed out in an amount of 1.5 g in a Schlenk flask under an inert gas atmosphere in a glove box, taken out of the glove box under an inert gas atmosphere, and heated at 180°C for 2 hours under a reduced pressure of 10 Pa or less to obtain a sulfide solid electrolyte (3). The XRD pattern of the sulfide solid electrolyte (3) is as shown in Figure 9, and it was confirmed that it contains a thiolicon region II type crystal structure. The ionic conductivity was 3.1 mS / cm.

[0151] Example 4 A sulfide solid electrolyte (4) was obtained in the same manner as in Example 1, except that 0.5 mmφ zirconia balls were used instead of 2 mmφ zirconia balls. The XRD pattern of the sulfide solid electrolyte (4) is as shown in Figure 10, and it was confirmed that it contained a thiolicon region II type crystal structure. The ionic conductivity was 4.1 mS / cm.

[0152] Example 5 A sulfide solid electrolyte (5) was obtained in the same manner as in Example 1, except that cyclohexane was used instead of dibutyl ether. The XRD pattern of the sulfide solid electrolyte (5) is as shown in FIG. 11, and it was confirmed that the sulfide solid electrolyte (5) contains a thiolicon region II type crystal structure. The ionic conductivity was 3.5 mS / cm.

[0153] (Examples 6 to 8) Using the Li3PS4-DME complex obtained in (2-3-2) and the LiI-DME complex obtained in (3-4-2), the amount of the Li3PS4-DME complex and the LiI-DME complex used was determined by taking the mass of Li3PS4 and the mass of LiI after the weight loss in TG-DTA, respectively, and weighing out a total of 2.0 g of each DME complex so that the molar ratio of Li3PS4:LiI was as shown in Table 1, and introducing it into a Schlenk tube (volume: 100 mL) with a stirrer. After rotating the stirrer, 20 mL of dibutyl ether was added. After continuing for 3 days, the mixture was dried at 50°C (room temperature: 23°C) to obtain a powder. Furthermore, the obtained powder was heated at 200°C under vacuum for 6 hours to obtain a crystalline sulfide solid electrolyte. The crystal structure of the crystalline sulfide solid electrolyte obtained in Examples 6 to 8 was confirmed from the XRD pattern.

[0154] It was confirmed that the crystalline sulfide solid electrolyte obtained in Example 6 contained a large amount of β-Li3PS4 crystal structure and Li4PS4I crystal structure, and contained a small amount of thiolicon region II type crystal structure. It was confirmed that the crystalline sulfide solid electrolyte obtained in Example 7 had a Li4PS4I crystal structure as the main phase, and contained a small amount of the β-Li3PS4 crystal structure and the thiolicon region II type crystal structure. It was confirmed that the crystalline sulfide solid electrolyte obtained in Example 8 had a Li4PS4I crystal structure as the main phase and contained a small amount of LiI crystal structure. The ionic conductivities of the crystalline sulfide solid electrolytes obtained in Examples 6 to 8 are shown in Table 1.

[0155] Comparative Example 1 The bead mill used was a "Bead Mill LMZ015" (manufactured by Ashizawa Finetech Co., Ltd.) and was charged with 485 g of zirconia balls with a diameter of 0.5 mm. A 2.0-liter glass reactor equipped with a stirrer was used as the reaction vessel. 34.77 g of Li2S obtained in (2-1-2) and 45.87 g of P2S5 obtained in (2-2-1) were charged into a reaction vessel, and 1000 mL of dehydrated toluene was further added to form a slurry. The slurry charged into the reaction tank was circulated at a flow rate of 600 mL / min using the pump in the bead mill apparatus. After starting operation of the bead mill at a peripheral speed of 10 m / s, 13.97 g of iodine (Wako Pure Chemical Industries, special grade) and 13.19 g of bromine (Wako Pure Chemical Industries, special grade) dissolved in 200 mL of dehydrated toluene were charged into the reaction tank.

[0156] After the addition of iodine and bromine, the peripheral speed of the bead mill was set to 12 m / s, and hot water (HW) was passed through the external circulation, and the temperature of the pump discharge was maintained at 70 ° C. The resulting slurry was subjected to a reaction so that the temperature of the pump discharge was maintained at 70 ° C. The resulting slurry was subjected to a supernatant liquid removal, and then placed on a hot plate and dried at 80 ° C. to obtain a powdered amorphous sulfide solid electrolyte. The resulting powdered amorphous sulfide solid electrolyte was heated at 195 ° C. for 3 hours using a hot plate installed in a glove box to obtain a sulfide solid electrolyte. The XRD pattern of the sulfide solid electrolyte was as shown in FIG. 9, and it was confirmed that the sulfide solid electrolyte contained a thiolicon region II type crystal structure. The ionic conductivity was 4.6 mS / cm.

[0157] From the XRD pattern results of FIGS. 9, 10 and 11, it was found that the sulfide solid electrolytes of Examples 1 to 5 and the sulfide solid electrolyte of Comparative Example 1 had similar crystal structures.

[0158] (Comparative Examples 2 to 4) In a 1L reactor equipped with an agitator, 15.3 g of the lithium sulfide and 24.7 g of the diphosphorus pentasulfide were added under a nitrogen atmosphere. After the agitator was operated, 400 mL of tetrahydrofuran previously cooled to -20°C was introduced into the vessel. After allowing the temperature to rise naturally to room temperature (23°C), stirring was continued for 72 hours, and the resulting reaction liquid slurry was poured into a glass filter (pore size: 40 to 100 μm) to obtain a solid content, which was then dried at 90°C to obtain 38 g of Li3PS4 (purity: 90 mass%) as a white powder. The XRD pattern of the obtained powder showed a halo pattern, and it was confirmed that the Li3PS4 was amorphous. The obtained Li3PS4 did not contain a complexing agent as a constituent component.

[0159] In a Schlenk flask (volume: 100 mL) with a stirrer, the amorphous Li3PS4 and the ground LiI obtained in (3-3) were weighed out in total and introduced in a nitrogen atmosphere so that the molar ratio of Li3PS4:LiI was as shown in Table 1. After rotating the stirrer, 20 mL of DME as a complexing agent was added. After three days, the mixture was dried at 50°C (room temperature: 23°C) to obtain a powder. The obtained powder was further heated at 200°C under vacuum for six hours to obtain a crystalline sulfide solid electrolyte. The crystal structures of the crystalline sulfide solid electrolytes obtained in Comparative Examples 2 to 4 were confirmed from the XRD patterns.

[0160] It was confirmed that the crystalline sulfide solid electrolyte of Comparative Example (2) contained a large amount of β-Li3PS4 crystal structure and Li4PS4I crystal structure, and a small amount of thiolicon region II type crystal structure. It was confirmed that the crystalline sulfide solid electrolyte of Comparative Example (3) had a Li4PS4I crystal structure as the main phase, and contained small amounts of the β-Li3PS4 crystal structure and the LiI crystal structure. It was confirmed that the crystalline sulfide solid electrolyte of Comparative Example (4) had a Li4PS4I crystal structure as the main phase and contained a small amount of LiI crystal structure. The ionic conductivities of the crystalline sulfide solid electrolytes of Comparative Examples (2) to (4) were as shown in Table 1.

[0161] [Table 1]

[0162] As shown in Examples 1 to 3, it was found that when complex (1) and complex (2) contain TMEDA as a constituent element, a sulfide solid electrolyte exhibiting extremely high ionic conductivity was obtained, as compared with the solid electrolyte obtained by the method described in Patent Document 1. In particular, it was found that a sulfide solid electrolyte exhibiting high ionic conductivity could be obtained even by simple methods such as Examples 2 (mixing without using a pulverizer) and 3 (dry mixing without using a solvent). Furthermore, it was found that even if the mixing conditions were changed (Example 4) or the solvent used was changed (Example 5), a sulfide solid electrolyte exhibiting similarly high ionic conductivity was obtained.

[0163] In addition, the solid electrolytes obtained in Comparative Examples 2 to 4 use DME as a complexing agent as in the manufacturing method described in Patent Document 4, but are solid electrolytes obtained without going through complexes (1) and (2) as in this embodiment. These manufacturing methods required a total of 84 hours of stirring. In contrast, even in the case of complexes (1) and (2) containing DME as a component as in Examples 6 to 8, sulfide solid electrolytes could be obtained in a much shorter time than in Comparative Examples 2 to 4. It was also confirmed that the sulfide solid electrolytes (6) to (8) exhibited higher ionic conductivity than the crystalline sulfide solid electrolytes obtained in the corresponding Comparative Examples (2) to (4).

[0164] (Reference: Exposure test) First, the test apparatus (exposure test apparatus 1) used in the exposure test will be described with reference to FIG. The exposure test apparatus 1 mainly comprises a flask 10 for humidifying nitrogen, a static mixer 20 for mixing humidified nitrogen and non-humidified nitrogen, a dew point meter 30 (M170 / DMT152 manufactured by VAISALA) for measuring the moisture content of the mixed nitrogen, a double reaction tube 40 in which a measurement sample is placed, a dew point meter 50 for measuring the moisture content of the nitrogen discharged from the double reaction tube 40, and a hydrogen sulfide meter 60 (Model 3000RS manufactured by AMI) for measuring the hydrogen sulfide concentration contained in the discharged nitrogen, and is configured to be connected by pipes (not shown). The temperature of the flask 10 is set to 10°C by a cooling tank 11. The tubes connecting the various components were made of Teflon (registered trademark) tubes with a diameter of 6 mm. In this diagram, the tubes are omitted, and instead the flow of nitrogen is indicated by arrows.

[0165] The evaluation procedure was as follows. About 1.5 g of powder sample 41 was weighed out in a nitrogen glove box with a dew point of −80° C., and placed and sealed inside reaction tube 40 so as to be sandwiched between quartz wool 42. Evaluation was performed at room temperature (20° C.).

[0166] Nitrogen was supplied from a nitrogen source (not shown) at 0.02 MPa into the apparatus 1. The supplied nitrogen passed through a bifurcated branch pipe BP, and a portion of it was supplied to the flask 10 and humidified. The remainder was supplied directly to the static mixer 20 as unhumidified nitrogen. The amount of nitrogen supplied to the flask 10 was adjusted by a needle valve V. The flow rates of non-humidified nitrogen and humidified nitrogen are adjusted with a flow meter FM equipped with a needle valve to control the dew point. Specifically, non-humidified nitrogen was supplied to the static mixer 20 at a flow rate of 800 mL / min and humidified nitrogen was supplied to the static mixer 20 at a flow rate of 10 to 30 mL / min, and mixed. The dew point of the mixed gas (a mixture of non-humidified nitrogen and humidified nitrogen) was confirmed with a dew point meter 30.

[0167] After adjusting the dew point to -30°C, the three-way cock 43 was rotated to allow the mixed gas to flow through the reaction tube 40 for two hours. The amount of hydrogen sulfide contained in the mixed gas that had passed through the sample 41 was measured with a hydrogen sulfide meter 60. The amount of hydrogen sulfide was recorded at 15-second intervals. For reference, the dew point of the mixed gas after exposure was also measured with a dew point meter 50. In order to remove hydrogen sulfide from the nitrogen after measurement, the nitrogen was passed through an alkali trap 70.

[0168] Exposure tests were carried out according to the above-mentioned exposure test method for the crystalline sulfide solid electrolyte obtained in Reference Example 1 below, the amorphous Li3PS4 obtained in Reference Example 2, and the crystalline sulfide solid electrolytes obtained in Reference Examples 3 and 4 below. Figure 13 is a graph showing the change over time in the amount of hydrogen sulfide generated, which was measured at regular intervals, and Figure 14 is a graph showing the change over time in the integrated amount of hydrogen sulfide generated, which was measured at regular intervals.

[0169] (Reference example 1) In Example 1, 1.70 g of the white powder obtained in Reference Example 2 below (Li3PS4: 1.53 g), 0.19 g of lithium bromide, and 0.28 g of lithium iodide were used, the amount of the complexing agent used was 4.4 mL, 15.6 mL of dibutyl ether was used as a solvent, and the stirring time was 24 hours. Except for this, a precursor, an amorphous sulfide solid electrolyte, and a crystalline sulfide solid electrolyte were obtained in the same manner as in Example 1. When the obtained crystalline sulfide solid electrolyte was subjected to powder X-ray diffraction (XRD) measurement in the same manner as in Example 1, it was found to have a thiolicon region II type crystal structure, and the ion conductivity was measured to be 4.3 mS / cm, which confirmed that the electrolyte had a high ion conductivity. In addition, since the complexes are not mixed in this Reference Example 1, a long stirring time is required, but the precursor, the amorphous sulfide solid electrolyte, and the crystalline sulfide solid electrolyte are similar to those of this embodiment.

[0170] (Reference example 2) In a 1L reactor equipped with an impeller, 15.3 g of lithium sulfide and 24.7 g of diphosphorus pentasulfide were added under a nitrogen atmosphere. After the impeller was operated, 400 mL of tetrahydrofuran, which had been cooled to -20°C in advance, was introduced into the vessel. After allowing the temperature to rise naturally to room temperature (23°C), stirring was continued for 72 hours, and the resulting reaction liquid slurry was poured into a glass filter (pore size: 40-100 μm) to obtain a solid content, which was then dried at 90°C to obtain 38 g of Li3PS4 (purity: 90% by mass) as a white powder. The resulting powder was subjected to powder XRD measurement using an XRD device (SmartLab device, manufactured by Rigaku Corporation), which showed a halo pattern and confirmed that it was amorphous Li3PS4.

[0171] (Reference example 3) The bead mill used was a "Bead Mill LMZ015" (manufactured by Ashizawa Finetech Co., Ltd.) and was charged with 485 g of zirconia balls with a diameter of 0.5 mm. A 2.0-liter glass reactor equipped with a stirrer was used as the reaction vessel.

[0172] 29.66g of lithium sulfide, 47.83g of diphosphorus pentasulfide, 14.95g of lithium bromide, 15.36g of lithium iodide, and 1200ml of dehydrated toluene were charged into the reaction vessel to form a slurry. The slurry charged into the reaction vessel was circulated at a flow rate of 600ml / min using the pump in the bead mill device, the operation of the bead mill was started at a peripheral speed of 10m / s, the peripheral speed of the bead mill was set to 12m / s, hot water (HW) was passed through by external circulation, and the temperature of the discharge of the pump was kept at 70°C to react. After removing the supernatant of the obtained slurry, it was placed on a hot plate and dried at 80°C to obtain a powdered amorphous sulfide solid electrolyte. The obtained powdered amorphous sulfide solid electrolyte was heated at 195°C for 3 hours using a hot plate installed in a glove box to obtain a crystalline sulfide solid electrolyte. The obtained crystalline sulfide solid electrolyte was subjected to powder X-ray diffraction (XRD) measurement, and it was confirmed that the electrolyte contained a thiolicon region II type crystal structure.

[0173] (Reference example 4) The bead mill used was a "Bead Mill LMZ015" (manufactured by Ashizawa Finetech Co., Ltd.) and was charged with 485 g of zirconia balls with a diameter of 0.5 mm. A 2.0-liter glass reactor equipped with a stirrer was used as the reaction vessel. 34.77g of lithium sulfide and 45.87g of diphosphorus pentasulfide were charged into the reaction vessel, and 1000ml of dehydrated toluene was added to make a slurry. The slurry charged into the reaction vessel was circulated at a flow rate of 600ml / min using the pump in the bead mill device, and the operation of the bead mill was started at a peripheral speed of 10m / s. Then, 13.97g of iodine (Wako Pure Chemical Industries, special grade) and 13.19g of bromine (Wako Pure Chemical Industries, special grade) dissolved in 200ml of dehydrated toluene were charged into the reaction vessel.

[0174] After the addition of iodine and bromine, the peripheral speed of the bead mill was set to 12 m / s, and hot water (HW) was passed through the external circulation, and the reaction was carried out so that the temperature of the pump discharge was maintained at 70 ° C. After removing the supernatant of the obtained slurry, the slurry was placed on a hot plate and dried at 80 ° C. to obtain a powdered amorphous sulfide solid electrolyte. The obtained powdered amorphous sulfide solid electrolyte was heated at 195 ° C. for 3 hours using a hot plate installed in a glove box, and a crystalline sulfide solid electrolyte was obtained. When the obtained crystalline sulfide solid electrolyte was subjected to powder X-ray diffraction (XRD) measurement, it was confirmed that it contained a thiolicon region II type crystal structure.

[0175] In the amorphous Li3PS4 obtained in Reference Example 2 above, the crystalline solid electrolyte obtained in Reference Example 3 by a conventional solid-phase method (mechanical milling method), and the crystalline solid electrolyte obtained in Reference Example 4 using a simple halogen as a raw material, hydrogen sulfide was generated at a maximum of 7 ppm, and the cumulative amount generated after 120 minutes exceeded 1 cc / g. It was confirmed, however, that almost no hydrogen sulfide was generated in the solid electrolyte obtained in Reference Example 1, which was produced using the same precursor as in this embodiment. [Industrial Applicability]

[0176] According to the method for producing a sulfide solid electrolyte of the present embodiment, it is possible to produce a crystalline sulfide solid electrolyte that has high ionic conductivity, is excellent in battery performance, and suppresses the generation of hydrogen sulfide. The crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment is suitably used for batteries, particularly for batteries used in information-related devices and communication devices such as personal computers, video cameras, and mobile phones.

Claims

1. A method for producing a sulfide solid electrolyte containing lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, comprising: Preparing a complex (1) containing a sulfide containing a lithium atom, a sulfur atom, and a phosphorus atom as a component, and a complex (2) containing a halide containing a lithium atom and a halogen atom as a component, respectively; mixing said complex (1) with said complex (2); The method for producing a sulfide solid electrolyte includes the steps of:

2. The method for producing a sulfide solid electrolyte according to claim 1, further comprising heating after mixing the complex (1) and the complex (2).

3. The method for producing a sulfide solid electrolyte according to claim 2, wherein the heating is performed at 90 to 250 ° C.

4. The method for producing a sulfide solid electrolyte according to claim 2 or 3, wherein the heating is performed at 0.1 to 100.0 Pa.

5. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 4, wherein the mixing is performed using a pulverizer.

6. The sulfide is amorphous Li 3 P.S. 4 Or crystalline Li 3 P.S. 4 The method for producing the sulfide solid electrolyte according to any one of claims 1 to 5, comprising:

7. The complex (1) further contains a complexing agent (1) as a component, and the complex (2) further contains a complexing agent (2) as a component. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 6.

8. The method for producing a sulfide solid electrolyte according to claim 7, wherein the complexing agent (1) and the complexing agent (2) each independently contain a compound having a heteroatom.

9. The method for producing a sulfide solid electrolyte according to claim 7 or 8, wherein the complexing agent (1) and the complexing agent (2) each independently contain a compound having at least one amino group or an ether bond.

10. The method for producing a sulfide solid electrolyte according to any one of claims 7 to 9, wherein the complexing agent (1) and the complexing agent (2) each independently contain a compound having at least two tertiary amino groups in a molecule.

11. The method for producing a sulfide solid electrolyte according to any one of claims 7 to 10, wherein the complex (1) and the complex (2) are mixed to obtain a precursor containing the complexing agent (1), the complexing agent (2), a lithium atom, a sulfur atom, a phosphorus atom, and a halogen atom as constituent components.

12. The method for producing a sulfide solid electrolyte according to claim 11, wherein the total content of the complex (1) and the complex (2) in the precursor is 30 to 80 mass% based on the total amount of the precursor.

13. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 12, wherein the mixing is carried out in a solvent.

14. The method for producing a sulfide solid electrolyte according to claim 13, wherein the solvent is at least one solvent selected from an aliphatic hydrocarbon solvent, an alicyclic hydrocarbon solvent, an aromatic hydrocarbon solvent, and an ether solvent.

15. The method for producing a sulfide solid electrolyte according to claim 13 or 14, wherein 5 to 50 mL of the solvent is used per 1 g of the total mass of the complex (1) and the complex (2).

16. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 15, wherein the sulfide solid electrolyte comprises a thiolicon region II type crystal structure.

17. The sulfide solid electrolyte is found to have crystalline Li 3 P.S. 4 The method for producing a sulfide solid electrolyte according to any one of claims 1 to 16, wherein the sulfide solid electrolyte does not have diffraction peaks at 2θ = 17.5 ° and 26.1 ° corresponding to the above.

Citation Information

Patent Citations

  • Liquid solution for formation of a solid electrolyte-containing layer of all-solid type lithium secondary battery, all-solid type lithium secondary battery, and method for manufacturing the same

    JP2014191899A

  • Manufacturing method of sulfide solid electrolyte

    JP2015056333A

  • Production method of sulfide solid electrolyte

    JP2017100907A

  • Method for producing sulfide solid electrolyte material

    JP2019102412A

  • Production method of solid electrolyte

    WO2014192309A1